Heat-resistant propylene-ethylene copolymers and adhesives containing propylene-ethylene copolymers
By developing characteristic propylene-ethylene copolyester, the problem of insufficient structural integrity and heat resistance in high-temperature applications has been solved, and good heat resistance and mechanical strength at high temperatures has been achieved, which meets the needs of high-temperature applications such as automotive interior components.
Patent Information
- Application Number
- JP2024553317
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-22
- Filing Date
- 2022-09-01
- Publication Date
- 2025-04-11
AI Technical Summary
Existing hot melt adhesives have problems with insufficient structural integrity and heat resistance in high-temperature applications, especially in automotive interior components, which are difficult to meet the needs of high-temperature environments.
A isomeric propylene-ethylene copolyester containing 89-98% propylene and 2-11% ethylene was developed. By adjusting the catalyst system and process conditions, its global softening point, stereoregularity and thermal crystallization heat are improved to enhance the thermal stability and mechanical strength of its hot melt adhesive.
It achieves good heat resistance and mechanical strength of hot melt adhesives at high temperatures, meets the needs of high-temperature applications such as automotive interior parts, and shows excellent thermal stability and adhesive strength in performance testing.
Smart Images

Figure 2025509264000001_ABST
Abstract
Description
[Technical field]
[0001] (Related Applications) This application is a continuation of U.S. Provisional Patent Application No. 63 / 269,737, filed March 22, 2022, entitled "HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS," U.S. Provisional Patent Application No. 63 / 269,738, filed March 22, 2022, entitled "PROCESS FOR MAKING HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS," U.S. Provisional Patent Application No. 63 / 269,742, filed March 22, 2022, entitled "COMPOSITIONS COMPRISING HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS," and U.S. Provisional Patent Application No. 63 / 269,742, filed March 22, 2022, entitled "PROPYLENE-ETHYLENE COPOLYMERS BASED HOT MELT COMPOSITIONS WITH IMPROVED HEAT This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 269,743, entitled "METHOD FOR HYDROXIDE RESISTANCE," the entire disclosures of which are incorporated herein by reference. [Background technology]
[0002] Hot melt adhesives used in high heat applications require structural integrity and durability at elevated temperatures and sub-ambient temperatures. An example is durable assembly applications such as appliances and automotive interior parts located above the seat belt line. In these demanding applications, polyester, polyamide, and moisture-curing polyurethane-based (PUR) hot melt reactive adhesives, solvent-based one-part reactive adhesives, and water-based polyurethanes (polyurethane dispersions) are frequently used.
[0003] Vehicle interior parts such as instrument panels and door trims typically contain olefin resins such as polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), and vinyl chloride as substrates, with a PP or urethane foam skin, typically a fabric or artificial leather covering, laminated to provide a good appearance and feel. Thermoplastic polyolefins compounds (TPOs), such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, are becoming more popular for parts in automotive interiors, such as instrument panels, center consoles, door panels, headliners, and interior trims.
[0004] Solvent-based modified chloroprene one-component reactive adhesives can provide excellent heat creep resistance properties. However, these chemicals are expensive and can be environmentally harmful, and there are still some drawbacks when using reactive hot melt adhesives, such as short pot life, narrow application temperature window, difficulty in balancing pot life and cure time, and long cure time, which can cause processing difficulties. In addition, these adhesives typically show poor adhesion to polyolefin substrates. The high cost combined with the potential health hazards associated with unreacted monomers in automotive interiors forces OEMs and compounders to look for polyolefin-based hot melt adhesives that can provide high temperature resistance and good adhesion to polyolefin-based substrates with good application temperature window.
[0005] It is desirable to have an adhesive with extended open time (the working time between the dispensing of the adhesive and the time when a bond between the substrates can no longer be formed) and good heat resistance (specifically measured by heat creep resistance). A practical heat resistance of about 80°C is typically required for interior vehicle parts. For example, US Patent Application Publication No. 2020 / 0017731 provides a polyolefin-based adhesive with heat creep resistance at 80°C. However, it has been observed that automobile dashboards can be exposed to temperatures as high as 90°C or 100°C.
[0006] Hot melt adhesive compositions containing amorphous-poly-alpha-olefins (i.e., APOs) or APO / isotactic polypropylene (IPP) blends are well known in the art and have good adhesion to polyolefin substrates without the presence of harmful monomers. APO-based adhesives typically consist of at least one APO and a hydrocarbon-type tackifier resin, and optionally contain a wax, which may be functionalized. However, it is well known that APO-based hot melt adhesives are not suitable for use in durable assembly applications, such as automotive interior parts, due to insufficient heat resistance and low cohesive strength. Recent developments have shown that improved APOs offer improved performance and can be formulated with a variety of polymers, tackifier resins, waxes, and oils, but there is still a need for APOs that have higher heat resistance while balancing improved mechanical strength and adhesion to desired substrates.
[0007] Amorphous propylene-ethylene copolymers made with Ziegler-Natta catalysts are known as useful components in hot melt adhesive applications. Such copolymers may be intermolecularly heterogeneous with respect to stereoregularity and / or composition. Furthermore, such copolymers may also be compositionally heterogeneous within the polymer chain. Such characteristics may, but are not always, the result of reactor process conditions and / or the type of catalyst system used. However, the tensile strength, elongation, and heat resistance of such copolymers are generally undesirable for use in heat resistant applications.
[0008] Furthermore, when formulating adhesive compounds for heat resistance, high melting / softening point polypropylene waxes can be added to the composition to improve temperature resistance, and it is known that as much as 14 weight percent of the formulation is PP wax with a melting point of at least 145°C. These waxes are typically very crystalline to achieve the desired high melting or softening point. However, these waxes are very brittle materials that are energy intensive to melt (as indicated by low penetration). Thus, polypropylene waxes with high stereoregularity and melting / softening points are generally poorly compatible with the main polyolefin polymer of the adhesive, and generally have low molecular weights, shortening the open time of the adhesive. Due to this incompatibility between the wax and the main polyolefin polymer, the resulting adhesive may exhibit poor cohesive strength, elongation, and viscosity.
[0009] Thus, there remains a need for polyolefin polymers that exhibit desirable heat resistance and manageable processing properties for use in adhesive compositions. Additionally, there is a need for polyolefin polymers that can produce adhesives with high heat resistance and high cohesive strength. Summary of the Invention
[0010] One or more embodiments of the present disclosure generally relate to a propylene-ethylene copolymer comprising propylene and ethylene, the propylene-ethylene copolymer further comprising: (a) 89-98 weight percent propylene, (b) a Ring and Ball softening point of at least 135° C., (c) a triad tacticity (mm%) of at least 50 percent, and (d) a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g.
[0011] With respect to the propylene-ethylene copolymer disclosed above, one or more embodiments of the present disclosure generally relate to an adhesive comprising the propylene-ethylene copolymer referenced above. As described above, the propylene-ethylene copolymer comprises (a) 89-98 weight percent propylene, (b) has a ring and ball softening point of at least 135°C, (c) has a triad tacticity (mm%) of at least 50 percent, and (d) has a heat of crystallization (Hc, cooling rate 20°C / min) of at least 25 J / g. Further, the adhesive comprises (a) 5-100 weight percent propylene-ethylene copolymer, (b) 0-90 weight percent of at least one second polymer, (c) 70 weight percent or less of at least one tackifier, (d) 20 weight percent or less of processing oil, and (e) 35 weight percent or less of at least one wax.
[0012] The following statements refer to various aspects of the disclosure. The following statements regarding aspects may be combined in any combination or may be applicable separately to the relevant aspects (e.g., one of the following limitations may be applicable to a first aspect, but another limitation may not be applicable to the first aspect).
[0013] According to a first aspect of the present disclosure, there is provided a propylene-ethylene copolymer comprising propylene and ethylene, the propylene-ethylene copolymer (a) comprising 89 to 98 weight percent propylene, (b) having a ring and ball softening point of at least 135° C., (c) having a triad tacticity (mm%) of at least 50 percent, and (d) having a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g.
[0014] In relation to the first embodiment, the propylene-ethylene copolymer may contain from 0.5 to 11 weight percent ethylene.
[0015] Additionally or alternatively, the propylene-ethylene copolymer has a viscosity of 1,000 to 50,000 cP at 190°C.
[0016] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 2,000 to 7,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 1.5 to 8 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0017] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 7,000 to 15,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 3 to 10 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0018] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 15,000 to 27,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 3 to 14 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0019] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of greater than 27,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of at least 7 MPa, and (d) a heat of crystallization of 25 to 50 J / g.
[0020] Additionally or alternatively, the propylene-ethylene copolymer has a ring and ball softening point in the range of 135 to 160°C.
[0021] Additionally or alternatively, the propylene-ethylene copolymer has a triad stereoregularity in the range of 50 to 70 percent.
[0022] Additionally or alternatively, the propylene-ethylene copolymer has a penetration in the range of 0.1 to 21 dmm.
[0023] Additionally or alternatively, the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 to 14 MPa.
[0024] Additionally or alternatively, the propylene-ethylene copolymer has an elongation at break of greater than 300 percent.
[0025] Additionally or alternatively, the propylene-ethylene copolymer has a heat of crystallization (Hc, cooling rate 20° C. / min) in the range of 20 to 55 J / g.
[0026] Additionally or alternatively, the propylene-ethylene copolymer (a) exhibits a penetration of 0.1 to 21 dmm; (b) has a heat of crystallization of 25 to 55 J / g; and (c) has the following: (i) having a viscosity of 2,000 to 7,000 cP at 190° C. and a tensile strength at break of 1.5 to 8 MPa; or (ii) having a viscosity of 7,000 to 15,000 cP at 190° C. and a tensile strength at break of 3 to 8 MPa; (iii) having a viscosity of 15,000 to 27,000 cP at 190° C. and a tensile strength at break of 3 to 14 MPa; or (iv) having one of the following characteristics: a viscosity of greater than 27,000 cP at 190° C., a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 to 50 J / g.
[0027] Additionally or alternatively, the propylene-ethylene copolymer (a) has a triad tacticity in the range of 53 to 78 percent, (b) exhibits a ring and ball softening point of 135 to 165° C., and (c) exhibits a heat of crystallization of 28 to 60 J / g.
[0028] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 15,000 to 50,000 cP at 190° C., (b) exhibits a tensile strength at break of at least 3 MPa, and (c) exhibits an elongation at break of at least 300 percent.
[0029] According to a second aspect of the present disclosure, there is provided a composition comprising a propylene-ethylene copolymer as discussed in the first aspect, as well as additions and alternatives with respect to the first aspect.
[0030] According to a third aspect of the present disclosure, there is provided a process for producing the propylene-ethylene copolymers discussed in the first aspect, as well as additions and alternatives relating to the first aspect, in the presence of a Ziegler-Natta catalyst system.
[0031] According to a fourth aspect of the present disclosure, there is provided an adhesive comprising: (a) from 5 to 100 weight percent of at least one propylene-ethylene copolymer, the propylene-ethylene copolymer comprising ethylene and propylene, (i) 89 to 98 weight percent propylene; (ii) having a Ring and Ball softening point of at least 135°C; (iii) having at least 50 percent triad tacticity (mm%); (iv) a propylene-ethylene copolymer having a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g; (b) 0 to 90 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 35 weight percent of at least one wax.
[0032] In accordance with the fourth embodiment, the adhesive composition comprises 5 to 55 weight percent of the second polymer.
[0033] Additionally or alternatively, the adhesive composition has (a) a shear adhesion failure temperature of at least 135°C, and / or (b) a thermal creep length at 110°C of 5 mm or less.
[0034] Additionally or alternatively, the adhesive composition has (a) a shear adhesion failure temperature of at least about 135°C, and (b) a thermal creep length at 120°C of 5 mm or less.
[0035] Additionally or alternatively, the adhesive composition includes (a) 10 to 70 weight percent of a propylene-ethylene copolymer; (b) 5 to 55 weight percent of a second polymer; (c) up to 70 weight percent of a tackifier; (d) up to 20 weight percent of a processing oil; and (e) up to 20 weight percent of a wax.
[0036] Additionally or alternatively, the adhesive composition includes (a) 5 to 95 weight percent of a propylene-ethylene copolymer; (b) 5 to 90 weight percent of a second polymer; (c) up to 70 weight percent of a tackifier; (d) up to 20 weight percent of a processing oil; and (e) up to 20 weight percent of a wax.
[0037] Additionally or alternatively, the adhesive composition includes (a) 30 to 80 weight percent of a propylene-ethylene copolymer; (b) 1 to 45 weight percent of a second polymer; (c) up to 70 weight percent of a tackifier; (d) up to 20 weight percent of a processing oil; and (e) up to 20 weight percent of at least one wax.
[0038] Additionally or alternatively, the adhesive composition comprises less than 10 weight percent wax.
[0039] Additionally or alternatively, the second polymer is selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor ready polyolefins, metallocene catalyzed polyolefin polymers and elastomers, reactor made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene catalyzed polypropylene polymers, metallocene catalyzed polyethylene polymers, propylene based terpolymers, copolymers made from propylene and linear or branched C4-C10 alpha-olefin monomers, copolymers made from ethylene and linear or branched C4-C10 alpha-olefin monomers, functionalized polyolefins, isoprene based block copolymers, butadiene based block copolymers, hydrogenated block copolymers, styrene-ethylene / butylene-styrene block copolymers. and at least one polymer selected from the group consisting of styrene-isoprene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene / propylene-styrene (SEPS), ethylene-vinyl acetate copolymer, polyester, polyester-based copolymer, neoprene, urethane, acrylic, polyacrylate, acrylate copolymer, polyether ether ketone, polyamide, hydrogenated styrene block copolymer, random styrene copolymer, ethylene-propylene rubber, ethylene-vinyl acetate copolymer, butyl rubber, styrene-butadiene rubber, butadiene-acrylonitrile rubber, natural rubber, polyisoprene, polyisobutylene, and polyvinyl acetate.
[0040] Additionally or alternatively, the propylene-ethylene copolymer may contain from 0.5 to 11 weight percent ethylene.
[0041] Additionally or alternatively, the propylene-ethylene copolymer has a viscosity of 1,000 to 50,000 cP at 190°C.
[0042] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 2,000 to 7,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 1.5 to 8 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0043] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 7,000 to 15,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 3 to 10 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0044] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 15,000 to 27,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of 3 to 14 MPa, and (d) a heat of crystallization of 25 to 55 J / g.
[0045] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of greater than 27,000 cP at 190° C., (b) exhibits a penetration of 0.1 to 21 dmm, (c) a tensile strength at break of at least 7 MPa, and (d) a heat of crystallization of 25 to 50 J / g.
[0046] Additionally or alternatively, the propylene-ethylene copolymer has a ring and ball softening point in the range of 135 to 160°C.
[0047] Additionally or alternatively, the propylene-ethylene copolymer has a triad stereoregularity in the range of 50 to 70 percent.
[0048] Additionally or alternatively, the propylene-ethylene copolymer has a penetration in the range of 0.1 to 21 dmm.
[0049] Additionally or alternatively, the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 to 14 MPa.
[0050] Additionally or alternatively, the propylene-ethylene copolymer has an elongation at break of greater than 300 percent.
[0051] Additionally or alternatively, the propylene-ethylene copolymer has a heat of crystallization (Hc, cooling rate 20° C. / min) in the range of 20 to 55 J / g.
[0052] Additionally or alternatively, the propylene-ethylene copolymer (a) exhibits a penetration of 0.1 to 21 dmm; (b) has a heat of crystallization of 25 to 55 J / g; and (c) has the following: (i) having a viscosity of 2,000 to 7,000 cP at 190° C. and a tensile strength at break of 1.5 to 8 MPa; or (ii) having a viscosity of 7,000 to 15,000 cP at 190° C. and a tensile strength at break of 3 to 8 MPa; (iii) having a viscosity of 15,000 to 27,000 cP at 190° C. and a tensile strength at break of 3 to 14 MPa; or (iv) having one of the following characteristics: a viscosity of greater than 27,000 cP at 190° C., a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 to 50 J / g.
[0053] Additionally or alternatively, the propylene-ethylene copolymer (a) has a triad tacticity in the range of 53 to 78 percent, (b) exhibits a ring and ball softening point of 135 to 165° C., and (c) exhibits a heat of crystallization of 28 to 60 J / g.
[0054] Additionally or alternatively, the propylene-ethylene copolymer (a) has a viscosity of 15,000 to 50,000 cP at 190° C., (b) exhibits a tensile strength at break of at least 3 MPa, and (c) exhibits an elongation at break of at least 300 percent.
[0055] According to a fifth aspect of the present disclosure, there is provided an article comprising the adhesive composition as discussed in the fourth aspect, as well as additions and alternatives with respect to the fourth aspect.
[0056] In relation to the fifth aspect, the article may be an adhesive, sealant, caulking, roofing membrane, waterproofing membrane, compound and underlayment, carpet, laminate, laminate article, tape, label, mastic, polymer blend, wire coating, molded article, heat seal coating, disposable sanitary article, insulating glass (IG) units, bridge decks, bitumen modification, asphalt modification, electronic enclosures, waterproofing membranes, cable flooding / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision casting, investment casting wax compositions, bookbinding, candles, windows, tires, films, gaskets, seals, O-rings, automobiles, motorcycles, automotive molded parts, automotive extrusion parts, clothing. materials, rubber additives / processing aids, and fibers, and the adhesive comprises a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile wrapping adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible lamination adhesive, a rigid lamination adhesive, a flexible film adhesive, a flexible packaging adhesive, a water activated adhesive, a household repair adhesive, an industrial adhesive, a building adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a cling film, a lamination adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven building adhesive, a sanitary core integrity adhesive, or a sanitary elastic attachment adhesive. [Brief description of the drawings]
[0057] Embodiments of the present invention are described herein with reference to the following drawings. [Figure 1] 1 is a graph comparing heat of crystallization and softening points of the copolymers and waxes of Tables 3A-3D. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] The present inventors have discovered a family of propylene-ethylene copolymers produced in the presence of Ziegler-Natta catalysts that can be readily utilized in high heat applications to form adhesives with improved mechanical strength and heat resistance. More specifically, the present inventors have discovered that propylene-ethylene copolymers with specific propylene content, isotacticity (i.e., triad stereoregularity), ring-and-ball softening point, and crystallinity exhibit desirable high heat resistance, tensile strength, and elongation. Furthermore, the present inventors have discovered that the unique isotacticity of the propylene-ethylene copolymers, as evidenced by the triad stereoregularity, is important in obtaining the desired heat resistance properties and improved mechanical properties.
[0059] These propylene-ethylene copolymers are produced by unique process conditions, more specifically, altered external donor / Ti ratios, and altered ethylene flow rates, along with adjustment of hydrogen flow rates in the presence of a Ziegler-Natta catalyst.
[0060] Furthermore, the inventors have discovered that these inventive propylene-ethylene copolymers can be used to produce adhesives that exhibit excellent heat resistance characteristics and excellent cohesive strength. More specifically, adhesives containing the inventive propylene-ethylene copolymers exhibit improved heat resistance and good peel strength in performance tests, which overcome the shortcomings of the prior art adhesives mentioned above. Adhesives containing the inventive propylene-ethylene copolymers exhibit excellent peel strength to the target substrate and excellent heat creep resistance at high temperatures.
[0061] The inventors have also discovered that the propylene-ethylene copolymers of the present invention have a unique balance of propylene content, isotacticity (as measured by triad tacticity), and softening point to provide a copolymer that can maintain a T-peel strength at 90°C and pass a thermal creep test at 110°C without the inclusion of propylene wax. Additionally, the inventors have discovered that as much as 20 weight percent polypropylene wax can be tolerated by the propylene-ethylene copolymers of the present invention. Furthermore, it has been discovered that adhesives containing the propylene-ethylene copolymers of the present invention can be formulated with 8 to 35 weight percent of a combination of polyethylene wax and polypropylene wax to adjust the viscosity, fiber tear adhesion, open time / set time, and other characteristics of the adhesive.
[0062] Heat-resistant propylene-ethylene copolymer In an embodiment, or in combination with any embodiment mentioned herein, there is provided a propylene-ethylene copolymer comprising propylene and ethylene, wherein the amount of propylene is in the range of 89% to 98% by weight, and the propylene-ethylene copolymer has a ring and ball softening point of 135° C. to 165° C., a triad tacticity (mm%) of 50 to 75%, and a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g.
[0063] In an embodiment, or in combination with any embodiment mentioned herein, there is provided a propylene-ethylene copolymer comprising propylene and ethylene, wherein the amount of propylene ranges from about 89% to about 98% by weight, the propylene-ethylene copolymer has a Ring and Ball softening point of about 135° C. to about 160° C., and the propylene-ethylene copolymer has a triad stereoregularity (mm %) of about 50 to about 70%.
[0064] According to various embodiments, the propylene-ethylene copolymers described herein may contain various amounts of ethylene. In some embodiments, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymers may contain at least 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11 weight percent ethylene based on the total weight of the copolymer. Additionally or alternatively, the propylene-ethylene copolymers may contain less than 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, or 3 weight percent ethylene based on the total weight of the copolymer.
[0065] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer can contain in the range of about 0.5 to about 11, about 0.5 to about 10, about 0.5 to about 9, about 0.5 to about 8, about 0.5 to about 7, about 0.5 to about 6, about 0.5 to about 5, about 0.5 to about 4, or about 0.5 to about 3, about 1 to about 11, about 1 to about 10, about 1 to about 9, about 1 to about 8, about 1 to about 7, about 1 to about 6, about 1 to about 5, about 1 to about 4, or about 1 to about 3 weight percent ethylene.
[0066] Further, in various embodiments, the propylene-ethylene copolymer may contain various amounts of propylene. In some embodiments, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may comprise at least 89, 90, 91, 92, 93, 94, 95, 96, 97, or 98 weight percent propylene, based on the total weight of the copolymer. Additionally or alternatively, the propylene-ethylene copolymer may comprise less than 98, 97, 96, 95, 94, 93, or 92 weight percent propylene, based on the total weight of the copolymer.
[0067] In an embodiment, or in combination with any embodiment referred to herein, the propylene-ethylene copolymer may be from about 89 to about 97, from about 89 to about 96, from about 89 to about 95, from about 89 to about 94, from about 89 to about 93, from about 89 to about 92, from about 89 to about 91, from about 90 to about 98, from about 90 to about 97, from about 90 to about 96, from about 90 to about 95, from about 90 to about 94, from about 90 to about 93, from about 90 to about 92, from about 91 to about 98, about 91 to about 97, about 91 to about 96, about 91 to about 95, about 91 to about 94, about 91 to about 93, about 92 to about 98, about 92 to about 97, about 92 to about 96, about 92 to about 95, about 92 to about 94, about 93 to about 97, about 93 to about 96, about 93 to about 95, about 94 to about 98, about 94 to about 97, about 94 to about 96, about 95 to about 98, about 95 to about 97, or about 96 to about 98 weight percent propylene.
[0068] The ethylene and propylene content of the copolymers is determined by NMR via the technique described by Wang et al. in Macromolecules 2000, 33, 1157-1162, which is incorporated herein by reference in its entirety.
[0069] In one embodiment, or in combination with any embodiment mentioned herein, the copolymer comprises one or more C4-C 10 It may contain alpha-olefins. Generally, C4-C 10 Alpha-olefins can be used to increase the resulting bond strength of the copolymer when utilized in adhesives. These C4-C 10 Alpha-olefins can include, for example, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and combinations thereof. According to one or more embodiments, the copolymers contain no more than 10, 8, 5, 3, 2, 1, 0.5, or 0.1 weight percent of at least one C4-C 10Further, in various embodiments, the copolymer may comprise at least one C4-C alpha-olefin in the range of 0.5 to 10, 1 to 10, 2 to 10, 3 to 10, 4 to 10, or 5 to 10 weight percent based on the total weight of the copolymer. 10 It may include an alpha-olefin.
[0070] In certain embodiments, the propylene-ethylene copolymer is any C4-C 10 It may also be free of alpha-olefins.
[0071] In general, the softening point of the propylene-ethylene copolymer can be modified and optimized by controlling the comonomer content, triad tacticity, crystallinity, and viscosity of the propylene-ethylene copolymer. A lower softening point of the copolymer may be desirable so that the copolymer can be utilized and processed at lower application temperatures. In some embodiments, or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may exhibit a ring and ball softening point of at least 135°C, 140°C, or 145°C, as measured according to ASTM E28 Standard Test Method for Softening Point of Resins Derived from Pine Chemicals and Hydrocarbons, by Ring-and Ball Apparatus, using a heating rate of 5°C per minute and a bath of USP glycerin. Additionally or alternatively, the propylene-ethylene copolymer may exhibit a ring and ball softening point of less than 165°C, 163°C, 160°C, 158°C, 155°C, 153°C, 150°C, 147°C, 145°C, or 140°C, when measured according to ASTM E28 Standard Test Method for Softening Point of Resins Derived from Pine Chemicals and Hydrocarbons, by Ring-and Ball Apparatus, using a heating rate of 5°C per minute and a bath of USP glycerin.
[0072] In certain embodiments, or in combination with any embodiment referred to herein, the copolymer has a melting point of about 135 to about 165° C., 135 to about 163° C., about 135 to about 160° C., 135 to about 158° C., about 135 to about 155° C., about 135 to about 153° C., about 135 to about 150° C., about 135 to about 147° C., about 135 to about 145° C., about 135 to about 140° C., about 140° C., or about 158° C. when measured according to the ASTM E28 Standard Test Method for Softening Point of Resins Derived from Pine Chemicals and Hydrocarbons, by Ring-and Ball Apparatus using a heating rate of 5° C. per minute and a USP glycerin or silicone oil bath liquid. The ring and ball softening point may be in the range of about 140 to about 165°C, about 140 to about 163°C, about 140 to about 160°C, about 140 to about 158°C, about 140 to about 155°C, about 140 to about 153°C, about 140 to about 150°C, about 140 to about 148°C, about 140 to about 145°C, about 145 to about 155°C, or about 145 to about 150°C.
[0073] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a triad tacticity of at least 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, or 65% mm content. Additionally or alternatively, the propylene-ethylene copolymer may have a triad tacticity of less than 78, 77, 76, 75, 74, 73, 72, 71, or 70, 69, 68, 67, 66, 65, 64, 63, 62, 61, or 60% mm content.
[0074] In some embodiments, or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a triad stereoregularity ranging from about 50 to about 78 mm content%, about 53 to about 78 mm content%, or about 50 to about 70 mm content%. Other ranges are about 50 to about 65 mm content%, about 50 to about 60 mm content%, about 50 to about 55 mm content%, about 55 to about 70%, about 55 to about 66 mm content%, about 55 to about 65 mm content%, about 55 to about 60 mm content%, about 60 to about 70%, or about 65 to about 70 mm content%.
[0075] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer is 52-78, 52-77, 52-76, 52-75, 52-74, 52-70, 52-65, 52-60, 53-78, 53-77, 53-76, 53-75, 53-74, 53-70, 53-65, 53-60, 54-78, 54-77, 54-76, 54-75, 54-74, 54-70, 54-67, 54-66, 54-65 , 54 to 60, 55 to 78, 55 to 77, 55 to 76, 55 to 75, 55 to 74, 55 to 70, 55 to 65, 55 to 60, 58 to 78, 58 to 77, 58 to 76, 58 to 75, 58 to 74, 58 to 70, 58 to 68, 60 to 78, 60 to 77, 60 to 76, 60 to 75, 60 to 74, 60 to 70, 60 to 68, 61 to 78, 61 to 77, 61 to 76, 61 to 75, 61 to 74, 61 to 70, or 61 to 68 mm content%.
[0076] The triad tacticity of a polymer is the relative tacticity of the sequence of three adjacent propylene units, a chain consisting of head-to-tail bonds, expressed as a binary combination of meso (m) and racemic (r) sequences. The methodology for measuring triad tacticity is described in the Examples section below.
[0077] Generally, the crystallinity of the propylene-ethylene copolymer can be determined via the heat of crystallization. In some embodiments, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer has a crystallinity of about 20 to about 30 J / g, about 20 to about 35 J / g, about 20 to about 40 J / g, about 20 to about 45 J / g, about 20 to about 50 J / g, about 20 to about 55 J / g, about 25 to about 30 J / g, about 25 to about 50 J / g, about 25 to about 55 J / g, about 27 to about 40 J / g, about 28 to about 30 J / g, about 29 to about 40 J / g, about 31 to about 35 J / g, about 32 to about 35 J / g, about 33 to about 35 J / g, about 34 to about 35 J / g, about 35 to about 40 J / g, about 36 to about 37 J / g, about 38 to about 38 J / g, about 39 to about 40 J / g, about 40 to about 45 J / g, about 40 to about 50 ... , about 28 to about 60 J / g, about 30 to about 35 J / g, about 30 to about 40 J / g, about 30 to about 45 J / g, about 30 to about 50 J / g, about 30 to about 55 J / g, about 35 to about 40 J / g, about 35 to about 45 J / g, about 35 to about 50 J / g, about 40 to about 45 J / g, about 40 to about 50 J / g, or about 40 to about 55 J / g.
[0078] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a heat of crystallization (Hc, cooling rate 20° C. / min, DSC) of at least 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40 J / g. Additionally or alternatively, the propylene-ethylene copolymer may have a heat of crystallization (Hc, cooling rate 20° C. / min, DSC) of less than 65, 64, 63, 62, 61, 60, 59, 58, 57, 56, 55, 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, or 40 J / g.
[0079] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer has a viscosity at 190° C. of about 1,000 to about 120,000 cP, about 1,000 to about 100,000, about 1,000 to about 75,000, about 1,000 to about 50,000, about 1,000 to about 45,000, about 1,000 to about 40,000, about 1,000 to about 35,000 cP, about 1,000 to about 30,000 cP, about 1,000 to about 25,000 cP, about 1,000 to about 20,000 cP, about 1,000 to about 15,000 cP, about 1,000 to about 10,000 cP, about 1,000 to about 5,000 cP , about 1,000 to about 3,000 cP, 2,000 to about 120,000 cP, about 2,000 to about 100,000, about 2,000 to about 75,000, about 2,000 to about 50,000, about 2,000 to about 45,000, about 2,000 to about 40,000, about 2,000 to about 35,000 cP, about 2,000 to about 3 The viscosity may be in the range of about 0,000 cP, about 2,000 to about 25,000 cP, about 2,000 to about 20,000 cP, about 2,000 to about 15,000 cP, about 2,000 to about 10,000 cP, about 2,000 to about 5,000 cP, about 2,000 to about 7,000 cP, or about 2,000 to about 3,000 cP.
[0080] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a low viscosity in the range of about 1,000 to about 7,000 cP (ASTM D-3236) at 190° C. Other low viscosity ranges at 190° C. are about 1,000 to about 5,000 cP, about 1,000 to about 3,000 cP, or about 2,000 to about 3,000 cP.
[0081] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a medium viscosity in the range of about 7,000 to about 15,000 cP at 190° C. Other medium viscosity ranges at 190° C. are about 7,000 to about 12,000 cP, about 7,000 to about 10,000 cP, or about 7,000 to about 9,000 cP.
[0082] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a high viscosity in the range of about 15,000 to about 27,000 cP at 190° C. Other high viscosity ranges at 190° C. are about 15,000 to about 25,000 cP, about 15,000 to about 20,000 cP, or about 15,000 to about 18,000 cP.
[0083] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have an ultra-high viscosity at 190° C. of greater than 27,000 cP, greater than 30,000 cP, greater than 35,000 cP, greater than 40,000 cP, greater than 45,000 cP, or greater than 50,000 cP. Other ultra-high viscosity ranges at 190°C are about 27,000 to about 150,000 cP, about 27,000 to about 125,000 cP, about 27,000 to about 100,000 cP, about 27,000 to about 75,000 cP, about 27,000 to about 70,000, about 27,000 to about 65,000, about 27,000 to about 60,000 cP, about 27,000 to about 55,000 cP, about 27,000 to about 50,000 cP, about 27,000 to about 45,000 cP, about 27,000 to about 40,000 cP, or about 27,000 to about 35,000 cP.
[0084] In general, the penetration of the propylene-ethylene copolymer can be modified and optimized by controlling the comonomer content, triad tacticity, and crystallinity of the propylene-ethylene copolymer. In some embodiments, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer can have a penetration in the range of about 0.1 to about 21 decimillilimeters ("dmm"), as measured according to ASTM D5. Other exemplary penetration ranges are 1 to 19 dmm, 1 to 16 dmm, 2 to 10 dmm, 2 to 8 dmm, 3 to 21 dmm, 3 to 19 dmm, 3 to 16 dmm, 3 to 10 dmm, 3 to 8 dmm, 4 to 21 dmm, 4 to 19 dmm, 4 to 16 dmm, 4 to 10 dmm, 4 to 8 dmm, 2 to about 21 dmm. Other ranges are 2-19 dmm, 2-16 dmm, 2-10 dmm, 2-8 dmm, 3-21 dmm, 3-19 dmm, 3-16 dmm, 3-10 dmm, 3-8 dmm, 4-21 dmm, 4-19 dmm, 4-16 dmm, 4-10 dmm, or 4-8 dmm.
[0085] In general, the tensile strength at break of the propylene-ethylene copolymer can be modified and optimized by controlling the comonomer content, triad tacticity, crystallinity, and viscosity of the propylene-ethylene copolymer. In some embodiments, or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer has a tensile strength of about 1.5 to about 25 MPa, about 1.5 to about 18 MPa, about 1.5 to about 17 MPa, about 3 to about 17 MPa, about 1.5 to about 14 MPa, about 3 to about 18 MPa, about 3 to about 15 MPa, about 3 to about 14 MPa, about 3 to about 12 MPa, about 3 to about 10 MPa, about 3 to about 8 MPa, about 3 to about 6 MPa, about 4 to about 14 MPa, about 4 to about 12 MPa, about 4 to about 10 ... a, the tensile strength at break (MPa) may be in the range of about 4 to about 8 MPa, about 4 to about 6 MPa, about 5 to about 14 MPa, about 5 to about 12 MPa, about 5 to about 10 MPa, 5 to about 8 MPa, about 6 to about 14 MPa, about 6 to about 12 MPa, about 6 to about 10 MPa, about 6 to about 8 MPa, about 7 to about 14 MPa, about 7 to about 12 MPa, about 7 to about 10 MPa, about 8 to about 14 MPa, or about 8 to about 12 MPa.
[0086] In some embodiments, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have an elongation at break (MPa) of greater than 100%, greater than 200%, greater than 300%, greater than 350%, greater than 375%, greater than 400%, greater than 425%, greater than 450%, greater than 475%, and greater than 500%, as measured according to ASTM D 412. For example, the propylene-ethylene copolymer may have an elongation at break (MPa) in the range of 300% to 2,000%, 300% to 1,000%, 300% to about 800%.
[0087] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer has a heat of fusion in the range of about 18 to about 45 J / g, about 10 J / g to about 36 J / g, about 10 to about 30 J / g, about 10 to about 25 J / g, about 10 to about 20 J / g, about 10 to about 15 J / g, 10 J / g to about 36 J / g, about 10 to about 30 J / g, about 10 to about 25 J / g, about 10 to about 20 J / g, about 10 to about 15 J / g, 15 J / g to about 36 J / g, about 15 to about 30 J / g, about 15 to about 25 J / g, about 15 to about 20 J / g, about 20 J / g to about 36 J / g, about 20 to about 30 J / g, or about 20 to about 25 J / g. fusion, Hf), heating rate 20° C. / min, DSC).
[0088] Table 1 shows various embodiments of propylene-ethylene copolymers. Generally, the ethylene copolymers of the present invention contain about 89 to about 98 weight percent propylene and have a Ring and Ball softening point of about 135° C. to about 165° C., a triad tacticity of about 50 to about 78%, and at least one other property selected from Table 1. For ease of reference, and not to be construed as limiting the invention, the polymers are designated in Tables 1A and 1B into four "families": (1) high viscosity, high tensile, and high RBSP polymers, (2) medium viscosity, high tensile, and high RBSP polymers, (3) very high viscosity and high RBSP polymers, and (4) low viscosity and high RBSP polymers.
[0089] [Table 1]
[0090] [Table 2]
[0091] In an embodiment, or in combination with any embodiment mentioned herein, the copolymers described herein do not exhibit substantial color change when subjected to storage conditions at high temperatures for extended periods of time. Before any storage-induced aging occurs, the copolymers of the present invention may have an initial Gardner color, as measured according to ASTM D1544, of less than 4, 3, 2, or 1. After heat aging at 177°C for at least 96 hours, the copolymers of the present invention may exhibit a final Gardner color, as measured according to ASTM D1544, of less than 7, 5, 3, or 2. Thus, the copolymers of the present invention may retain desirable color even after extended storage and exposure.
[0092] Additionally, the copolymers described herein can be amorphous or semi-crystalline. As used herein, "amorphous" means that the copolymer has less than 5 percent crystallinity as measured using Differential Scanning Calorimetry ("DSC") according to ASTM E 794-85. As used herein, "semi-crystalline" means that the copolymer has a crystallinity in the range of 5 to 40 percent as measured using DSC according to ASTM E 794-85 at a scan rate of 20°C / min. In various embodiments, the copolymer can have a crystallinity of 60, 40, 30, 20, 10, 5, 4, 3, 2, or 1 percent or less as measured using DSC according to ASTM E 794-85 at a scan rate of 20°C / min. Additionally or alternatively, the copolymer may have a crystallinity of less than 60, 50, 45, 40, 35, 30, 25, 24, 23, or 22 percent, as measured using DSC at 20° C. / min according to ASTM E 794-85. For example, the copolymer may have a crystallinity in the range of 2 to 50, 3 to 46, 4 to 40, 4 to 30, 4 to 20, 16 to 25, 16 to 23, 17 to 25, 17 to 23, 20 to 35, or 20 to 30 percent, as measured using DSC at 20° C. / min according to ASTM E 794-85.
[0093] Process for producing propylene-ethylene copolymers The objective of the present invention is to provide a family of propylene-ethylene copolymers that can be used in high heat resistant applications and exhibit improved mechanical strength. Without wishing to be bound by theory, it is believed that the unique heat resistance and ability to support loads at high temperatures is obtained due to the combination of several different copolymer characteristics, such as the propylene / ethylene content of the copolymer, the triad tacticity content (mm%) of the copolymer, the ring and ball softening point of the copolymer, and the heat of crystallization of the copolymer. The objective of the present invention is met by a specific range of polymer compositions, more specifically, the propylene / ethylene comonomer ratio, together with a preferred range of propylene triad tacticity content (mm%). These polymer compositions are met by improved process conditions.
[0094] In an embodiment, or in combination with any embodiment mentioned herein, the copolymer may be produced by reacting propylene and ethylene monomers in the presence of a catalyst system that includes at least one electron donor.
[0095] In some embodiments, or in combination with any of the embodiments mentioned herein, the catalyst system may include a Ziegler-Natta catalyst. According to one or more embodiments, the Ziegler-Natta catalyst may include a titanium-containing component, an aluminum component, and an electron donor. In certain embodiments, the catalyst includes titanium chloride on a magnesium chloride support.
[0096] The catalyst system may, in certain embodiments, comprise a heterogeneous supported catalyst system formed from a titanium compound in combination with an organoaluminum cocatalyst. In various embodiments, the cocatalyst may comprise an alkylaluminum cocatalyst, such as triethyl aluminum ("TEAL").
[0097] In one or more embodiments, the catalyst system may have an aluminum to titanium molar ratio of at least 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or 15:1, and / or up to 100:1, 50:1, 35:1, or 25:1. Further, the catalyst system may have an aluminum to titanium molar ratio ranging from 1:1 to 100:1, 5:1 to 50:1, 10:1 to 35:1, or 15:1 to 25:1. Additionally or alternatively, in various embodiments, the catalyst system may have an aluminum to silicon molar ratio of at least 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, or 6:1, and / or up to 100:1, 50:1, 35:1, 20:1, 15:1, 10:1, or 8:1. Additionally, the catalyst system may have a molar ratio of aluminum to silicon ranging from 0.5:1 to 100:1, 1:1 to 50:1, 2:1 to 35:1, 2:1 to 20:1, 2:1 to 15:1, 2:1 to 10:1, or 2:1 to 8:1.
[0098] Electron donors can increase the stereospecificity of the copolymer. However, it may be important to strictly control the content of electron donors, as they may suppress the catalytic activity to an unacceptable level in some circumstances. Electron donors used during the polymerization process may include, for example, organic esters, ethers, alcohols, amines, ketones, phenols, phosphines, and / or organosilanes. Furthermore, the catalyst system may include internal donors and / or external donors.
[0099] There are many generations of internal donors for Ziegler-Natta catalyst systems, as defined in "Stereospecific α-Olefin Polymerization with Heterogeneous Catalysts," by J. Severn and RL Jones Jr, Handbook of Transition Metal Polymerization Catalysts, (2018) Chapter 9, p229-312, which is incorporated herein by reference in its entirety. The generations of Ziegler-Natta catalysts are described by Severn and Jones as follows:
[0100] Ziegler-Natta Catalysts Generation 3 (Benzoates): Generation 3 catalysts typically contain MgCl2, TiCl4, and an internal electron donor, which are combined with an aluminum alkyl cocatalyst, such as Al(CH2CH3)3. An "external" electron donor may be added to the catalyst system. The internal donor in Generation 3 catalysts is typically ethyl benzoate, which is used in combination with a second aromatic ester, such as methyl p-toluate or ethyl p-ethoxybenzoate (PEEB), as the external donor. The external donor is required due to the fact that most of the internal donor is lost as a result of reactions involving cocatalysis, such as alkylation and / or complexation reactions. For the most part, the external donor replaces the internal donor in the solid catalyst, maintaining high catalytic stereospecificity.
[0101] Ziegler-Natta Catalysts Generation 4 (Phthalate): Generation 4 catalysts contain MgCl2, TiCl4, and an internal electron donor, which are combined with an aluminum alkyl cocatalyst such as Al(CH2CH3)3. An "external" electron donor can be added to the catalyst system. The internal donor in the Generation 4 catalyst is a phthalate / alkoxysilane system. It was found that the bidentate phthalate donor can form a strong chelate complex with the tetracoordinate Mg atom on the (110) face of MgCl2, or a binuclear complex with the two pentacoordinate Mg atoms on the (100) face.
[0102] Ziegler-Natta catalysts, 5th generation (diethers and succinates): Certain diether compounds, especially those with oxygen-oxygen distances of 2.8 to 3.2
[0103]
number
[0104] Ziegler-Natta Catalysts 6th Generation (Phthalate Replacement): The new 1,2-phenylenedibenzoate internal donors used in 6th generation Ziegler-Natta catalysts are important as phthalate replacements. In addition, there is an increasing disclosure of mixed internal donors, such as blends of succinates and diethers, or blends of succinates and dimethoxytoluenes. 6th generation catalysts can also provide high stereospecificity in the absence of external donors. Thus, depending on the crystallinity target, an external donor may or may not be used to reach the desired crystallinity target.
[0105] In some embodiments, or in combination with any of the embodiments mentioned herein, the third and higher generation Ziegler-Natta catalyst systems may be operated in the absence of an external electron donor. Depending on the crystallinity target, an external donor may or may not be used to reach the desired crystallinity target when using fifth and sixth generation catalyst systems.
[0106] In certain embodiments, or in combination with any of the embodiments mentioned herein, the catalyst system may include a third generation Ziegler-Natta catalyst, a fourth generation Ziegler-Natta catalyst, a fifth generation Ziegler-Natta catalyst, or a sixth generation Ziegler-Natta catalyst.
[0107] Generally, the catalyst system includes at least one external electron donor. In some embodiments, or in combination with any of the embodiments mentioned herein, the external electron donor includes at least one alkoxysilane, such as a "D" donor (e.g., dicyclopentyldimethoxysilane), a "C" donor (e.g., cyclohexylmethyldimethoxysilane), or a combination thereof. Furthermore, in some embodiments, the alkoxysilane can include, consist essentially of, or consist entirely of a "D" donor or a "C" donor.
[0108] In one embodiment of the present invention, no electron donor is utilized in the process.
[0109] It has been observed that the addition of the external donor to the catalyst system can increase the hardness (i.e., decrease the needle penetration) and increase the viscosity of the copolymer. However, contrary to what has been previously observed in the art, the electron donor can decrease the softening point of the copolymer produced instead of increasing it. Furthermore, it has been observed that substantially all (i.e., more than 95 percent) of the ethylene added to the reactor during the polymerization process can react when the electron donor is used. This can therefore result in a copolymer with a higher ethylene content and a lower propylene content. As a result, when the electron donor is used, a propylene-ethylene copolymer can be produced that has a higher ethylene content but still exhibits the desired balance between softening point and hardness.
[0110] Additionally, according to various embodiments, the catalyst system may have a molar ratio of external electron donor to titanium of at least 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, or 4:1, and / or less than 10:1, 9:1, or 8:1. Additionally or alternatively, the catalyst system may have a molar ratio of external electron donor to titanium of at least 0.1:1 to 10:1, 0.5:1 to 10:1, 1:1 to 10:1, 1.5:1 to 10:1, 2:1 to 10:1, 2.5:1 to 10:1, 3:1 to 10:1, 3.5:1 to 10:1, 4:1 to 10:1, 0.5:1 to 9:1, 1:1 to 9:1, 1.5:1 to 9:1, 2:1 The molar ratio of external electron donor to titanium may range from 0.5:1 to 8:1, 1:1 to 8:1, 1.5:1 to 8:1, 2:1 to 8:1, 2.5:1 to 8:1, 3:1 to 8:1, 3.5:1 to 8:1, or 4:1 to 8:1.
[0111] Additionally or alternatively, in various embodiments, the catalyst system can include a molar ratio of TEAL cocatalyst to electron donor of at least 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, or 6:1, and / or no greater than 100:1, 50:1, 35:1, 20:1, 15:1, 10:1, or 8:1. Further, the catalyst system can include a molar ratio of TEAL cocatalyst to electron donor in the range of 0.5:1 to 100:1, 1:1 to 50:1, 2:1 to 35:1, 2:1 to 20:1, 2:1 to 15:1, 2:1 to 10:1, or 2:1 to 8:1.
[0112] In certain embodiments, the type of electron donor can affect the required TEAL / electron donor ratio, for example, in embodiments where the electron donor is a "D" donor or a "C" donor, the TEAL / electron donor ratio can be less than 20:1.
[0113] The catalyst system may exhibit catalytic activities ranging from 200-2,000, 400-1,200, 500-1,000, 1,000-6,000, or 6,000-18,000 g / g. The catalytic activity is calculated by measuring the ratio of the weight of polymer made in the reactor to the weight of catalyst loaded in the reactor. These measurements are based on a reaction time of 1 hour.
[0114] Because the addition of external donors can increase viscosity and molecular weight, the addition of hydrogen may be required to act as a chain terminator during polymerization. For example, the process may be run at hydrogen pressures ranging from 5 to 100, 10 to 80, or 15 to 50 psig.
[0115] In certain embodiments, or in combination with any embodiment mentioned herein, the polymerization reaction may occur at a temperature in the range of 160° C. or less, 155° C. or less, 150° C. or less, or 145° C. or less, 140° C. or less, 100-200, 110-180, 110-155, 120-160, 140-155, or 120-150° C. Additionally, the polymerization reaction may be carried out at a pressure in the range of 500-2,000, 600-1,500, 700-1,250, or 800-1,100 psig.
[0116] In an embodiment of the present invention, the ratio of ethylene flow rate to propylene flow rate to the polymerization reaction is 0.1:100 to 18:100, 0.1:100 to 10:100, 0.1:100 to 5:100, 0.1:100 to 4:100, 0.5:100 to 3:100, 0.5:100 to 2:100, 0.5:100 to 1.5:100, 0.5:100 to 1:100, 1:100 to 4:100, 1:100 to 3:100, 1:100 to 2:100, 1.5:100 to 4:100, 1.5:100 to 3:100, 1.5:100 to 2:100, 2:100 to The ratio may be in the range of 4:100, 2:100 to 3:100, 3:100 to 18:100, 3:100 to 14:100, 3:100 to 12:100, 3:100 to 10:100, 4:100 to 18:100, 4:100 to 14:100, 4:100 to 12:100, 4:100 to 10:100, 7:100 to 18:100, 7:100 to 14:100, 7:100 to 12:100, 7:100 to 10:100, 8:100 to 18:100, 8:100 to 14:100, 8:100 to 12:100, or 8:100 to 10:100.
[0117] In an embodiment of the present invention, the ratio of hydrogen flow rate to propylene flow rate to the polymerization reaction may be in the range of 0.03:100 to 0.5:100, 0.04:100 to 0.4:100, 0.15:100 to 0.4:100, 0:100 to 0.3:100, 0:100 to 0.2:100, 0.100:100 to 0.02:100, 0:100 to 0.01:100, 0.01:100 to 0.02:100, 0.04:100 to 0.2:100, 0.05:100 to 0.1:100, 0.07:100 to 0.3:100, or 0.08:100 to 0.4:100.
[0118] In certain embodiments, the reactor may comprise a stirred reactor and the polymerization reaction may have a residence time in the reactor ranging from 0.1 to 6, 0.5 to 4, or 1 to 2 hours. In some embodiments, the polymerization reaction may have a residence time in the reactor ranging from 6 to 72, 16 to 36, 16 to 24, 12 to 48, or 12 to 24 hours. In other embodiments, the reactor may comprise a loop reactor and the polymerization reaction may have a residence time in the reactor ranging from 8 to 72, 12 to 48, 12 to 24, or 16 to 36 hours. In some embodiments, or in combination with any embodiment mentioned herein, ethylene may be added to the reactor as a gas and propylene may be added as a liquid.
[0119] End Uses Containing Heat Resistant Propylene-Ethylene Copolymers The inventive propylene-ethylene copolymers and compositions comprising these copolymers described herein can be used in, for example, adhesives (e.g., automotive adhesives, woodworking adhesives, packaging adhesives), sealants, caulkings, roofing membranes, waterproofing membranes, compounds and underlayments, carpets, laminates, laminated articles, tapes (e.g., tamper evident tapes, water activated tapes, pressure sensitive tapes, sealing tapes, scrim reinforced tapes, veneer tapes, reinforced and non-reinforced adhesive paper tapes, box maker tapes, paper tapes, packaging tapes), labels, mastics, polymer blends, wire coatings, molded articles, heat seals, adhesives, and the like. The compositions may be utilized in a wide range of applications including coatings, disposable sanitary articles, insulating glass (IG) units, bridge decks, bitumen modification, asphalt modification, cable flooding / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, plastic fiber reinforced compounds, wood plastic composites, lost wax precision casting, investment casting wax compositions, candles, windows, films, gaskets, seals, O-rings, automotive molded parts, automotive extrusion parts, apparel, rubber additives / processing aids, and fibers.
[0120] Films comprising the propylene-ethylene copolymers of the present invention and compositions comprising these copolymers described herein include, but are not limited to, multilayer films, coextruded films, calendered films, and cast films.Laminates comprising the propylene-ethylene polymers of the present invention or compositions comprising the propylene-ethylene polymers of the present invention include, but are not limited to, paper-foil laminates, paper-film laminates, and nonwoven-film laminates.
[0121] Adhesive compositions comprising the inventive propylene-ethylene copolymers described herein and compositions comprising these copolymers include packaging adhesives, food contact grade adhesives, indirect food contact packaging adhesives, product assembly adhesives, woodworking adhesives, edge banding adhesives, profile wrapping adhesives, flooring adhesives, automotive assembly adhesives, structural adhesives, mattress adhesives, pressure sensitive adhesives (PSA), PSA tapes, PSA labels, PSA protective films, cling films, laminating adhesives, flexible packaging adhesives, heat seal adhesives, industrial adhesives, sanitary nonwoven construction adhesives, sanitary core integrity adhesives, and sanitary elastic attachment adhesives.
[0122] In certain embodiments, the copolymers described herein can be utilized in adhesives such as, for example, hot melt adhesives, water-based adhesives, solvent-based adhesives, hot melt pressure-sensitive adhesives, solvent-based pressure-sensitive adhesives, hot melt nonwoven / hygienic adhesives, hot melt product assembly adhesives, hot melt woodworking adhesives, hot melt automotive assembly adhesives, hot melt lamination adhesives, and hot melt packaging adhesives. In particular, the adhesives produced from the copolymers of the present invention can be utilized in numerous end products, including hygienic packaging, appliances, automotive parts, woodworking, and packaging applications that require heat resistance, due to the unique combination of softening point, heat resistance, and penetration as described above. In many embodiments, the various properties (e.g., softening point and penetration) of the copolymers of the present invention can be selected to suit the intended end use of the composition incorporating the heat-resistant copolymers of the present invention.
[0123] In certain embodiments, the copolymers of the present invention may be used to produce adhesive compositions useful in automotive interior assembly, packaging, product assembly, heat sealing, lamination, gap sealing, e.g., cable filling, caulking, and window sealants, wood working, edge banding, and / or profile wrapping. The terms "adhesive," "adhesive composition," and "composition" are used interchangeably.
[0124] In an embodiment, or in combination with any embodiment mentioned herein, the adhesive composition of the present invention comprises a hot melt adhesive. The hot melt adhesive can be applied to a substrate while in its molten state and allowed to cool to harden the adhesive layer. Such adhesives are widely used in various commercial and industrial applications, such as product assembly, lamination, and packaging. In these applications, the adhesive is applied to at least one substrate to bond the substrate to a second similar or dissimilar substrate.
[0125] Adhesive, sealant, and other formulators and users generally desire thermally stable, low color hot melt adhesives that have a favorable balance of physical properties including temperature resistance, chemical resistance, cohesive strength, viscosity, adhesion to various substrates, and open and cure times that can be tailored to specific use and application conditions. The balance of desired properties varies depending on the application, and the inventive hot melt compositions described herein provide an improved balance of properties for multiple end uses.
[0126] The hot melt adhesive composition may have a melt rheology and thermal stability suitable for use in conventional hot melt adhesive application equipment. In some embodiments, or in combination with any of the embodiments mentioned herein, the blended components of the hot melt adhesive composition have a low melt viscosity at the application temperature, which facilitates the flow of the composition through the coating equipment, such as a coating die or nozzle.
[0127] The hot melt adhesive compositions are useful for bonding a variety of substrates including, for example, cardboard, coated cardboard, paperboard, fiberboard, virgin and recycled kraft, high and low density kraft, chipboard, treated and coated kraft and chipboard and corrugated versions thereof, clay coated chipboard carton stock, composites, leather, polymeric films (e.g., polyolefin films (e.g., polyethylene and polypropylene), polyvinylidene chloride films, ethylene vinyl acetate films, polyester films, metallized polymeric films, multilayer films, and combinations thereof), fibers and substrates made from fibers (e.g., virgin fibers, recycled fibers, synthetic polymeric fibers, cellulose fibers, and combinations thereof), release liners, porous substrates (e.g., woven webs, nonwoven webs, nonwoven scrims, and perforated films), cellulosic substrates, sheets (e.g., paper and fiber sheets), paper products, tape backings, and combinations thereof. Useful composites include, for example, chipboard laminated to a metal foil (e.g., aluminum foil), which may optionally be laminated to at least one layer of polymeric film, chipboard bonded to a film, kraft bonded to a film (e.g., polyethylene film), and combinations thereof.
[0128] Hot melt adhesive compositions can be used in, for example, articles including packaging, bags, boxes, cartons, cases, trays, multi-wall bags, accessories (e.g., straws attached to beverage boxes), ream wraps, cigarettes (e.g., plug wraps), filters (e.g., pleated filters and filter frames), bookbinding, footwear, disposable absorbent articles (e.g., disposable diapers, sanitary napkins, medical dressings (e.g., wound care products), bandages, surgical pads, drapes, gowns, and meat packaging products), paper products (e.g., paper towels (e.g., multiple use The adhesives are useful for bonding a first substrate to a second substrate in a variety of applications and constructions, including paper towels, toilet paper, facial tissue, wipes, tissue, towels (e.g., paper towels), sheets, veneers, mattress covers, automotive foils, TPO compounds, and components of absorbent articles (e.g., absorbent elements, absorbent cores, impermeable layers (e.g., backsheets), tissues (e.g., packaging tissue), acquisition layers, and woven and nonwoven web layers (e.g., topsheets, absorbent tissue), and combinations thereof.
[0129] The hot melt adhesive compositions are also useful for forming laminates of porous substrates and polymeric films, such as those used in the manufacture of disposable articles including, for example, medical drapes, medical gowns, sheets, feminine hygiene articles, diapers, adult incontinence articles, absorbent pads for animals (e.g., pet pads) and humans (e.g., body and cadaver), and combinations thereof.
[0130] The hot melt adhesive composition may be applied to a substrate in any useful form, including, for example, as a fiber, as a coating (e.g., continuous and discontinuous coatings (e.g., random, pattern, and array), as a bead, as a film (e.g., continuous and discontinuous films), and combinations thereof, using any suitable application method, including, for example, slot coating, curtain coating, spray coating (e.g., spiral spray, random spray, and random fiberization (e.g., melt blowing)), foaming, extrusion (e.g., bead application, fine wire extrusion, single screw extrusion, and twin screw extrusion), wheel application, non-contact coating, contact coating, gravure, engraved roller, roll coating, transfer coating, screen printing, flexography, and combinations thereof.
[0131] One embodiment of the present invention relates to a vehicle having a vehicle interior material (preferably an automobile interior material) including a skin material (preferably a polyolefin-based substrate) to which a hot melt composition is applied. Examples of the vehicle according to the present invention include, but are not limited to, automobiles, motorcycles, buses, trucks, and streetcars. In this specification, the term "automobile interior material" is used in some sentences, but it can be interpreted as meaning an interior material for vehicles other than automobiles as long as the hot melt composition of the present invention can be applied.
[0132] The compositions of the present invention may be used to form bonds to produce laminates and multi-layer laminates. The terms "laminate" and "multi-layer laminate" may be used interchangeably.
[0133] The inventive composition according to one or more embodiments of the present invention may be applied to cellulosic polymeric materials such as paper, cotton, linen, cloth, and wood board; polyolefin resins such as polypropylene (PP) and polyethylene (PE), styrene resins such as polystyrene, styrene-butadiene block copolymer (SBS resin), styrene-acrylonitrile copolymer (AS resin), acrylonitrile-ethylene / propylene-styrene copolymer (AES resin), and acrylonitrile-butadiene-styrene copolymer (ABS resin), polycarbonate resin (PC resin), and synthetic polymeric materials including PC-ABS resin. It can be bonded to a variety of adherends, including, but not limited to, (meth)acrylic resins, polyester resins, polyamide resins such as nylon and polyurethane, phenolic resins, and epoxy resins, wood materials, metal materials, plastic materials, elastomer materials, composite materials, paper materials, textile materials, glass materials, foam materials, metals, mesh materials, leather materials, synthetic leather materials, vinyl materials, poly(acrylonitrile butadiene styrene) (ABS), polypropylene (PP), glass-filled PP, talc-filled PP, impact-modified PP, urethane elastomers, thermoplastic polyolefin (TPO) compounds, colored TPO compounds, filled TPO compounds, rubber-modified TPO compounds, and undercoat (paint) materials. The material of the adherend may be a mixture or combination of two or more different materials. When forming a laminate by bonding two different adherends via an adhesive layer comprising the propylene-ethylene polymer of the present invention or the hot melt adhesive of the present invention, the materials of the two adherends may be the same or different from each other.
[0134] Laminates containing the polymer or composition of the present invention can be suitably used in applications in which coating materials and formed articles are used as adherends, such as interior materials for automobiles and the like (e.g., automobile interior ceiling materials, automobile interior door parts, automobile interior dashboard parts, instrument panels), home appliance parts (e.g., personal computer housings, flat-screen television frames), and housing materials (e.g., interior wall panels, decorative films, etc.).
[0135] Covering materials refer to any type of film, sheet, foam, or nonwoven or woven material. Examples include decorative polymer sheets made of polyvinyl chloride, various polyolefins, ABS, thermoplastic polyolefin compounds (TPO), such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, polyester nonwoven fabrics, brushed knits, woven fabrics, polyurethane artificial leather, and polyolefin foams made mainly of polypropylene, polyethylene, polybutylene, or copolymers of these olefins. Examples of molded products include injection molded products of various polymer materials such as ABS, PC / ABS, polyolefin, glass fiber reinforced polyolefin, and glass fiber reinforced nylon; and wood molded products and wood boards prepared by enveloping materials such as wood chips or wood powder in thermosetting resin or polyolefin resin by hot press molding.
[0136] When preparing a multi-layer laminate by bonding a coating material such as a decorative sheet to a molded article used as a substrate through an adhesive layer containing the propylene-ethylene polymer or hot melt adhesive composition of the present invention, various forming methods such as heat lamination, vacuum forming, vacuum pressure forming, hot pressing, hot rolling, hot stamping, etc. A curved molded article refers to a molded article made from the above material, in which the bonding surface with the coating material has a flat arc-shaped surface. Such a molded article is used to form a shape framework in an automobile interior or a housing of a home appliance.
[0137] In an embodiment, or in combination with any embodiment mentioned herein, there is provided a process, in which at least one composition useful in the present invention can be applied to a first substrate, or can be applied to two or more substrates, each substrate can be independently selected, and the first substrate and the second substrate can each be independently selected from the group consisting of poly(acrylonitrile butadiene styrene) (ABS); polycarbonate (PC); PC-ABS blend; thermoplastic polyolefin such as polypropylene (PP); TPO compound; fabric, for example, woven material, mesh, plywood, birch, veneer, MDF board, woven fabric, and / or nonwoven fabric; foam material; leather material; vinyl material; and / or others that will be obvious to those skilled in the art.These materials can be used with or without fillers.
[0138] Typical, but non-limiting, industrial applications of the hot melt adhesive composition include packaging for high temperature use, such as cases and cartons in warehouses, woodworking, and vehicle (e.g., automobile) interior part assembly. Traditional end-use applications such as bookbinding, sanitary disposable consumer goods, and labeling would also benefit from the end-use heat resistance and efficiency of automated means of applying the hot melt adhesive composition to various substrates.
[0139] Additionally, in various embodiments, the inventive copolymers described herein may also be used to modify existing polymer blends typically utilized in plastics, elastomer applications, roofing applications, asphalt modification, cable filling, and tire modification, and may improve the adhesion, processability, stability, viscoelasticity, thermal, and mechanical properties of these polymer blends.
[0140] In some embodiments, or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymers of the present invention can be modified to produce graft copolymers. In such embodiments, the copolymers of the present invention can be grafted with maleic anhydride, fumaric and maleic acid esters, methacrylic acid esters (e.g., glycidyl methacrylate and hydroxyethyl methacrylate), methacrylic acid, vinyl derivatives, silane derivatives, or combinations thereof. These graft copolymers can be produced using any conventional process known in the art, including, for example, transesterification and free radical induced coupling.
[0141] The various end uses and end products discussed above may utilize the copolymer of the present invention by itself or may combine it with other additives and polymers. Suitable polymers that can be combined with the copolymers of the present invention to form polymer blends may include, for example, isoprene-based block copolymers; butadiene-based block copolymers; hydrogenated block copolymers; styrene-ethylene / butylene-styrene block copolymers (SEBS); styrene-isoprene-styrene block copolymers (SIS); styrene-ethylene / propylene-styrene (SEPS); ethylene vinyl acetate copolymers; polyesters; polyester-based copolymers; neoprene; urethanes; acrylics; polyacrylates; acrylate copolymers, such as, but not limited to, ethylene acrylic acid copolymers, ethylene n-butyl acrylate copolymers, and ethylene methyl acrylate copolymers; polyether ether ketones; polyamides; styrene block copolymers; hydrogenated styrene block copolymers; random styrene copolymers; ethylene-propylene rubber; ethylene vinyl acetate copolymers; butyl rubber; styrene butadiene rubber; butadiene acrylonitrile rubber; natural rubber; polyisoprene; polyisobutylene; polyvinyl acetate; and polyolefins.
[0142] The polyolefins used in the present invention together with the propylene-ethylene copolymers of the present invention can be any known in the art. In some embodiments, or in combination with any of the embodiments mentioned herein, the polyolefins can be amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers including ethylene-propylene-butylene terpolymers, propylene and linear or branched C4-C 10 Copolymers made from alpha-olefin monomers, ethylene and linear or branched C4-C 10 It can be at least one selected from the group consisting of copolymers made from alpha-olefin monomers, and functionalized polyolefins.
[0143] There are multiple methods in the art for functionalizing polymers that may be used with the polymers described herein. These include selective oxidation, free radical grafting, ozonolysis, epoxidation, etc. Functionalized components include functionalized olefin polymers (functionalized C2-C 40 Homopolymer, Functionalized C2-C 40Functionalized olefin polymers and copolymers useful in the present invention include, but are not limited to, maleated polyethylene, maleated metallocene polyethylene, maleated metallocene polypropylene, maleated ethylene propylene rubber, maleated polypropylene, maleated ethylene copolymers, functionalized polyisobutylene (typically functionalized with maleic anhydride to typically form succinic anhydride), and the like.
[0144] In some embodiments, or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymers of the present invention described herein can be used to produce hot melt adhesives. According to one or more embodiments, the adhesive composition can comprise at least 1, 5, 6, 7, 8, 9, 10, 15, 20, 23, 25, 30, 35, 37, 40, 45, 47, or 50, and / or no more than 95, 90, 85, 80, 76, 75, 70, 66, 63, 60, 59, 56, 55, 52, 50, 45, 40, 35, 30, 25, 20, 15, or 10 weight percent of the copolymer of the present invention. Further, the adhesive composition may comprise in the range of 1-95, 5-90, 10-80, 20-70, 30-60, 40-55, 50-80, 50-70, 30-90, 30-80, 30-70, 30-60, 30-50, or 30-40 weight percent of the copolymer of the present invention. In certain embodiments, the adhesive composition may consist entirely of the copolymer of the present invention.
[0145] Additionally, depending on the intended end use, these hot melt adhesive compositions may also contain a variety of additives including, for example, polymers, tackifiers, processing oils, waxes, antioxidants, plasticizers, pigments, and fillers.
[0146] In certain embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may comprise at least 1, 5, 6, 7, 10, 12, 20, 23, 30, 35, 40, or 47, and / or up to 90, 80, 70, 56, or 55 weight percent of at least one polymer different from the copolymer of the present invention. Additionally, the adhesive may comprise in the range of 10-90, 20-80, 30-70, or 40-55 weight percent of at least one polymer different from the copolymer of the present invention. In other embodiments, the adhesive may comprise at least 1, 5, 6, 7, 8, 9, 10, 15, 20, 23, 25, 30, 35, 40, 45, 47, or 50 weight percent of at least one polymer different from the copolymer of the present invention. These polymers may include, but are not limited to, any of the polymers listed above.
[0147] Furthermore, it has been found that blends of the copolymers of the present invention with various types of polyolefins can provide the adhesive with improved adhesion, cohesive strength, temperature resistance, viscosity, and open and cure times. Thus, in various embodiments, the above-mentioned polymers that can be combined with the propylene-ethylene copolymers of the present invention can include at least one polyolefin. In certain embodiments, the adhesive can include at least 1, 5, 6, 7, 10, 12, 15, 20, 23, 25, 30, 35, 40, 45, 47, or 50 weight percent of at least one polyolefin in addition to the propylene-ethylene copolymers of the present invention. Additionally or alternatively, the adhesive composition can include up to 99, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 7, or 5 weight percent of at least one polyolefin in addition to the propylene-ethylene copolymers of the present invention. For example, the adhesive composition may include at least one polyolefin in the range of 1-90, 1-60, 1-40, 1-20, 10-90, 20-80, 20-40, 30-70, 30-40, or 40-55 weight percent based on the total weight. In one or more embodiments, the polyolefins may be amorphous polyolefins having a heat of fusion of less than 25 J / g or less than 15 J / g. In one or more embodiments, the polyolefins may be metallocene-catalyzed polyolefin polymers.
[0148] Commercially available examples of acceptable polyolefins include Aerafin™ 17 by Eastman; Aerafin™ 180 by Eastman; Rextac™ polymers made by REXtac LLC, including REXtac™ E-63, E-65, 2760, 2815, 2730, and 2830; polymers made by Evonik Industries, including Vestoplast®, Vestoplast® 408 and 708; and Eastoflex® by Eastman, including Eastoflex® E1060 and P1010.
[0149] Some examples of metallocene-catalyzed polymers include polyolefins such as polyethylene, polypropylene, and copolymers thereof. Exemplary polypropylene-based elastomers include those sold under the trade name VISTAMAXX™ by ExxonMobil Chemical and those sold under the trade name L-MODU™ by Idemitsu Kosan (Japan), and exemplary polyethylene-based elastomers and plastomers include those sold under the trade names AFFINITY™, AFFINITY™ GA, INFUSE™, and ENGAGE™ by Dow Chemical Company, those sold under the trade name VISTAMAXX™ by ExxonMobil Chemical Company (Houston, Texas), and those sold under the trade name LlCOCENE™ by Clariant.
[0150] In some embodiments, or in combination with any of the embodiments mentioned herein, the olefin polymer comprises a mixture of at least two different olefin polymers, such as a blend comprising an olefin homopolymer and an olefin copolymer, a blend comprising different olefin homopolymers of the same or different monomers, a blend comprising different olefin copolymers, and various combinations thereof. Useful olefin polymers also include, for example, modified, unmodified, grafted, and ungrafted olefin polymers, unimodal olefin polymers, multimodal olefin polymers, and combinations thereof.
[0151] In some embodiments, or in combination with any of the embodiments mentioned herein, these added polyolefins may increase the cohesive strength, adhesive properties, tack, low temperature flexibility, total crystallinity, and / or temperature resistance of the adhesive composition of the present invention. Furthermore, the addition of said polyolefins may reduce the production costs of the composition due to their widespread availability.
[0152] In certain embodiments, an adhesive composition may include the propylene-ethylene copolymer of the present invention and a metallocene-catalyzed polyethylene copolymer, such as an ethylene-octene copolymer. In such embodiments, the propylene-ethylene copolymer of the present invention may be used to replace polyethylene in various types of adhesives, such as those used in packaging applications.
[0153] In certain embodiments, the added polymer and / or polyolefin may be functionalized at the polymer chain ends and / or at pendant positions within the polymer with groups including, but not limited to, silane, anhydride such as maleic anhydride, hydroxyl, ethoxy, epoxy, siloxane, amine, amine siloxane, carboxy, and acrylate.
[0154] The additional polymers and polyolefins that may be added to the adhesive compositions of the present invention may be prepared by Ziegler-Natta catalysts, single-site catalysts (metallocene), multiple single-site catalysts, non-metallocene heteroaryl catalysts, combinations thereof, or by another polymerization means. The additional polymers may include combinations of amorphous, semi-crystalline, random, branched, linear, or block structures.
[0155] Any conventional polymerization synthesis process may prepare the additional polyolefin component. In one or more embodiments, one or more catalysts, typically metallocene or Ziegler-Natta catalysts, are used to polymerize the olefin monomer or monomer mixture. Polymerization methods include high pressure, slurry, gas, bulk, suspension, supercritical, or solution phase, or combinations thereof. The catalyst may be in the form of a homogeneous solution, supported, or combinations thereof. The polymerization may be carried out by continuous, semi-continuous, or batch processes and may include the use of chain transfer agents, scavengers, or other such additives as deemed applicable. In one or more embodiments, the additional polymer is produced in a single or multiple polymerization zones using a single polymerization catalyst. Metallocene (or heterophasic) polymers are typically made using multiple metallocene catalyst blends to obtain the desired heterophasic structure.
[0156] In some embodiments, or in combination with any of the embodiments mentioned herein, the crystalline content of the added polymer or polyolefin can increase the cohesive strength of the adhesive composition. In general, a compound based on a metallocene-polymerized semi-crystalline copolymer can eventually build up a sufficient crystalline content over time to achieve good cohesive strength in the compound.
[0157] In certain embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may comprise at least 5, 10, 15, 20, 25, 30, 35, 40, or 45, and / or no more than 90, 80, 70, 55, 50, 45, or 40 weight percent of at least one tackifier. Additionally, the adhesive may comprise in the range of 5-90, 20-80, 20-40, 20-30, 30-70, or 40-55 weight percent of at least one tackifier. The tackifier may provide tack to the adhesive and reduce the viscosity of the adhesive. Lower viscosity may improve application flow characteristics, allowing easier processing, lower energy requirements, and lower processing temperatures. Lower viscosity also helps the adhesive to "wet out" or coat a surface substantially evenly and penetrate the substrate. Tack is required in most adhesive formulations to allow proper joining of articles before solidification of the hot melt adhesive. The desirability and selection of a particular tackifier may depend on the particular type of olefin copolymer and additional polymer used.
[0158] Suitable tackifiers may include, for example, cycloaliphatic hydrocarbon resins, C5 hydrocarbon resins; C5 / C9 hydrocarbon resins; aromatic modified C5 resins; C9 hydrocarbon resins; pure monomer resins such as styrene or copolymers with alpha-methylstyrene, vinyl toluene, para-methylstyrene, indene, methylindene, C5 resins, and C9 resins; terpene resins; terpene phenolic resins; terpene styrene resins; rosin esters; modified rosin esters; fully or partially hydrogenated rosin liquid resins; fully or partially hydrogenated rosin esters; fully or partially hydrogenated modified rosin resins; fully or partially hydrogenated rosin alcohols; fully or partially hydrogenated C5 resins; fully or partially hydrogenated C5 / C9 resins; fully or partially hydrogenated aromatic modified C5 resins; fully or partially hydrogenated C9 resins; fully or partially hydrogenated pure monomer resins; fully or partially hydrogenated C5 / cycloaliphatic resins; fully or partially hydrogenated C5 / cycloaliphatic / styrene / C9 resins; fully or partially hydrogenated cycloaliphatic resins; and combinations thereof. Exemplary commercially available hydrocarbon resins include Regalite™ hydrocarbon resins (Eastman Chemical). In certain embodiments, the tackifier may include a functionalized tackifier.
[0159] In some embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may include at least 1, 2, 5, 8, or 10, and / or no more than 40, 30, 25, 20, or 15 weight percent of at least one processing oil. Additionally, the adhesive may include at least one processing oil in the range of 2 to 40, 5 to 30, 8 to 25, or 10 to 20 weight percent. The processing oil may include, for example, mineral oil, naphthenic oil, paraffin oil, aromatic oil, castor oil, rapeseed oil, triglyceride oil, or combinations thereof. As will be appreciated by those skilled in the art, the processing oil may also include extender oils that are typically used in adhesives. The use of oils in the adhesive may be desirable when the adhesive is used as a pressure sensitive adhesive to produce tapes or labels, or as an adhesive to bond nonwoven articles. In certain embodiments, the adhesive may not include any processing oil.
[0160] In certain embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may comprise at least 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, and / or up to 40, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, or 15 weight percent of at least one wax. Further, the adhesive may comprise 0-15, 1-40, 5-30, 8-25, 10-20, 1-25, 1-20, 1-15, 1-10, or 1-5 weight percent of at least one wax. The wax serves to reduce the overall viscosity of the adhesive, thereby liquefying the adhesive and allowing for proper application or coating of the hot melt adhesive onto the intended substrate. The type and melting point of the wax, as well as its compatibility with the other components of the adhesive composition, control the open time and cure speed of the adhesive. Open time is known in the art as the length of time that the adhesive wets out and bonds to the substrate after application. Any conventional known wax suitable for use in formulating hot melt adhesives may be used in the practice of the present invention.
[0161] In certain embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may comprise at least 1, 2, 3, 4, or 5 percent by weight of polyethylene wax, polypropylene wax, maleated polyolefin wax, or a combination of two or more thereof. Additionally or alternatively, the adhesive composition may comprise no more than 40, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 percent by weight of polyethylene wax, polypropylene wax, maleated polyolefin wax, or a combination of two or more thereof.
[0162] Suitable waxes may include, for example, microcrystalline waxes, paraffin waxes, waxes produced by the Fischer-Tropsch process, functionalized waxes (such as maleated waxes, fumarated waxes, or waxes with functional groups), polyolefin waxes, petroleum waxes, polypropylene waxes, polyethylene waxes, ethylene vinyl acetate waxes, and vegetable waxes. When the adhesive is used as a hot melt packaging adhesive, the use of waxes in the adhesive may be desirable.
[0163] Non-limiting examples of commercially available waxes suitable for the present invention include SasolWax® H-1 available from Sasol Wax Americas, Inc.; AC™-9, AC-596, and AC 810 available from Honeywell International Inc.; EPOLENE™ N-15 and E-43 available from Westlake Chemical; and POLYWAX™ 400, 850, 1000, and 3000 from Baker Hughes Inc. Other exemplary waxes include, but are not limited to, Clariant Licocene™ PE4201; Westlake EPOLENE™ C-10, EPOLENE™ C-17, and EPOLENE™ C-18; and microcrystalline wax Be Square™ 195.
[0164] As used herein, "functionalized" means that the component is prepared in the presence of a functional group that is incorporated into the component or is contacted with the functional group and optionally a catalyst, heat, initiator, or free radical source to incorporate, graft, bond, physically attach, and / or chemically attach all or a portion of the functional group (such as maleic acid or maleic anhydride) to the polymer.
[0165] Exemplary functionalized wax polymers useful as functionalized components include those modified with alcohols, acids, ketones, anhydrides, and the like. Commercially available functionalized waxes include maleated polypropylene available under the tradename MAPP40 from Chusei; maleated metallocene waxes (such as TP LICOCENE PP1602 available from Clariant); maleated polyethylene and polypropylene waxes available under the tradenames EPOLENE C-16, EPOLENE C-18, EPOLENE E43 from Westlake; EASTMAN G-3003 from Eastman Chemical; maleated polypropylene wax LICOMONT AR 504 available from Clariant; grafted functional polymers available under the tradenames AMPLIFY EA 100 and AMPLIFY VA 200 from Dow Chemical Co.; and CERAMER™ maleated ethylene polymers available under the tradenames CERAMER 1608, CERAMER 1251, CERAMER 67, and CERAMER 24 from Baker Hughes. Useful waxes also include polyethylene and polypropylene waxes having a Mw of less than 15,000, preferably 3,000 to 10,000, a crystallinity of 5% by weight or more, preferably 10% by weight or more, and a functional group content of up to 10% by weight. Additional functionalized polymers that may be used as functional components include AC 575P, AC 573P, A-CΧ596A, A-CΧ596P, A-CΧ597A, A-CΧ597P, A-CΧ950P, A-CΧ1221, AC 395A, AC 395A, AC 1302P, AC 540, AC 54A, AC 629, AC 629A, AC 307, and AC 307A available from Honeywell International Inc.
[0166] In certain embodiments, the adhesive composition may be free of wax, for example, the adhesive composition may contain less than 10, 5, 4, 3, 2, or 1 weight percent of a wax, such as, but not limited to, a polyethylene wax and / or a Fischer-Tropsch wax.
[0167] In certain embodiments, or in combination with any embodiment mentioned herein, the adhesive composition may include at least 0.1, 0.2, 0.5, 1, 2, or 3, and / or no more than 20, 10, 8, 5, 1, or 0.5 weight percent of at least one antioxidant. Further, the adhesive composition may include in the range of 0.1 to 20, 1 to 10, 2 to 8, or 3 to 5 weight percent of at least one antioxidant.
[0168] In some embodiments, or in combination with any of the embodiments mentioned herein, the adhesive composition may include at least 0.5, 1, 2, or 3, and / or up to 20, 10, 8, or 5 weight percent of at least one plasticizer. Additionally, the adhesive may include in the range of 0.5 to 20, 1 to 10, 2 to 8, or 3 to 5 weight percent of at least one plasticizer. Suitable plasticizers may include, for example, olefin oligomers, low molecular weight polyolefins such as liquid polybutylene, polyisobutylene, mineral oil, dibutyl phthalate, dioctyl phthalate, chlorinated paraffins, and non-phthalate-containing plasticizers. Commercially available plasticizers may include, for example, Benzoflex™ plasticizer (Eastman Chemical); Eastman 168™ (Eastman Chemical); Oppanol® B10 (BASF); REGALREZ 1018 (Eastman Chemical); Calsol 5550 (Calumet Lubricants); Kaydol oil (Chevron); or ParaLux oil (Chevron).
[0169] In certain embodiments, or in combination with any embodiment mentioned herein, the adhesive composition may include at least 10, 20, 30, or 40, and / or up to 90, 80, 70, or 55 weight percent of at least one filler. Further, the adhesive may include in the range of 1 to 90, 20 to 80, 30 to 70, or 40 to 55 weight percent of at least one filler. Suitable fillers may include, for example, carbon black, calcium carbonate, clay, titanium oxide, zinc oxide, or combinations thereof.
[0170] The adhesive composition can be produced using conventional techniques and equipment. For example, the components of the adhesive composition can be blended in a mixer such as a sigma blade mixer, a plasticorder, a Brabender mixer, a twin screw extruder, or an in-can blend (pint can). In some embodiments, or in combination with any of the embodiments mentioned herein, the adhesive can be formed into a desired form, such as a tape or sheet, by a suitable technique, including, for example, extrusion, compression molding, calendaring, or roll coating techniques (e.g., gravure, reverse roll, etc.), curtain coating, slot die coating, or spray coating.
[0171] Additionally, the adhesive composition can be applied to the substrate by a solvent casting process or by melting the adhesive and then using conventional hot melt adhesive application equipment known in the art. Suitable substrates can include, for example, nonwoven fabrics, woven fabrics, paper, glass, plastics, films (polyethylene, polypropylene, polyester, etc.), and metals. Generally, the adhesive composition can be applied at a coating weight of about 0.1 to 100 g / m 2 , about 0.1~about 150g / m 2 , or about 1 to about 1000 g / m 2 The adhesive composition may be applied to a substrate.
[0172] According to one or more embodiments, the hot melt adhesive composition may have a Brookfield viscosity at 177° C. of at least 100, 300, 500, 750, or 1,000, and / or no more than 60,000, 40,000, 30,000, 20,000, 10,000, 5,000, 4,000, 3,000, or 2,500 cps, as measured according to ASTM D3236. Further, the hot melt adhesive may have a Brookfield viscosity in the range of 100-60,000, 300-10,000, 500-5,000, 750-2,500, 400-3,000, 500-1,000, 500-5,000, 500-10,000, 500-15,000, 500-20,000, 1,000-5,000, 1,000-10,000, 1,000-15,000, 1,000-20,000, 1,000-40,000, 1,000-60,000 cps at 177°C.
[0173] In an embodiment, or in combination with any embodiment mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 190° C. of at least 100, 500, 1,000, 2,000, 3,000, 4,000, 5,000, 6,000, 7,000, 8,000, or 9,000, and / or no more than 60,000, 50,000, 40,000, 30,000, 20,000, 15,000, or 10,000 cps, as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 190° C. in the range of 100 to 60,000, 500 to 30,000, 1,000 to 40,000, 1,000 to 10,000, 2,000 to 20,000, 2,000 to 10,000, 2,000 to 15,000, 3,000 to 15,000, 2,500 to 25,000, or 2,000 to 30,000 cps.
[0174] Further, in various embodiments, the hot melt adhesive composition may have a 90 degree peel strength (T-peel) of at least 1, 2, 5, 10, or 15, and / or no more than 50, 40, 35, 30, or 25 g / mm, as measured according to ASTM D903. Further, the hot melt adhesive may have a peel strength in the range of 1-50, 2-40, 5-35, 10-30, or 15-25 g / mm, as measured according to ASTM D903. Additionally or alternatively, the hot melt adhesive may have a 90 degree peel strength of at least 0.05, 0.1, 0.2, or 0.5, and / or no more than 20, 10, 5, or 1 lbf / inch, as measured according to ASTM D903.
[0175] According to various embodiments, adhesive compositions containing the copolymers of the present invention may have a wide operating window and may have an application window of 80-230° C. This wide operating window may be demonstrated by the peel strength of the adhesive at different temperatures.
[0176] In an embodiment, or in combination with any embodiment mentioned herein, the hot melt adhesive composition may have a holding power of at least 0.1, 0.5, or 1, and / or no more than 50,000, 10,000, 5,000, 1,000, 500, 100, 50, 20, 10, 7, or 4 hours at 50° C., as measured according to ASTM D3654. Further, the hot melt adhesive may have a holding power in the range of 0.1 to 10, 0.5 to 7, or 1 to 4 hours at 50° C., as measured according to ASTM D3654.
[0177] In other embodiments, the hot melt adhesive composition may exhibit a holding strength of at least 5, 15, 20, or 25 minutes, and / or up to 150 minutes at 60°C. Additionally or alternatively, the hot melt adhesive may exhibit a holding strength of at least 400, 600, 800, or 1,000 minutes at 50°C. Holding strength at 50°C and 60°C may be measured by stabilizing the glued carton substrate overnight at room temperature (usually 20-23°C) and then suspending the substrate in a shear bank oven in peel mode. A weight is then suspended under the glued substrate. The time at which the weight falls due to failure is recorded for each specimen.
[0178] The hot melt adhesive composition may exhibit a shear adhesion failure temperature ("SAFT") of at least 2, 3, 30, 50, 75, 80, 85, 90, 95, 100, 110, 120, 130, 135, and / or no more than 200, 160, 155, 150, 140, 135, 134, 133, 130, or 135°C, as measured according to ASTM D4498. Additionally, the hot melt adhesive may have a SAFT in the range of 2-200, 30-200, 50-150, 75-125, 130-160, 130-155, 130-150, 130-145, 135-155, 135-150, 140-160, 140-155, 140-150, 145-160, 145-155, or 145-150° C., as measured according to ASTM D4498.
[0179] In an embodiment, or in combination with any embodiment mentioned herein, the hot melt adhesive composition may exhibit a high temperature performance fiber tear ("HTFT") of at least 50, 65, 70, 75, 80, 85, 90, or 95 percent at 60°C. The HTFT test consists of manually tearing a glued corrugated paper (carton) substrate by hand under 60°C conditions. The glued carton substrate must be stabilized under 60°C conditions for 4 hours ± 5 minutes before tearing. If 80% of the fibers of the substrate break, the test is considered to be passed and the hot melt adhesive is therefore considered to perform well. In some applications, if 50% of the fibers of the substrate break, the test is considered to be passed and the adhesive is considered to perform well at 60°C.
[0180] In an embodiment, or in combination with any embodiment mentioned herein, the adhesive containing the copolymer of the present invention does not exhibit substantial color change when subjected to storage conditions at high temperatures for extended periods of time. Before any storage-induced aging occurs, the adhesive may have an initial Gardner color, measured according to ASTM D1544, of less than 18, 15, 10, 8, 5, 4, 3, 2, or 1. After heat aging at 177°C for at least 96 hours, the adhesive may exhibit a final Gardner color, measured according to ASTM D1544, of less than 18, 15, 10, 7, 5, 3, 2, or 1. Thus, the adhesive may retain a desirable color even after extended storage and exposure.
[0181] In an embodiment, or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer of the present invention may be utilized in an adhesive composition as previously described in this disclosure. In particular, the propylene-ethylene copolymer of the present invention may be utilized to produce a hot melt adhesive having a wide process window and high peel strength for laminate materials, such as, but not limited to, dashboard parts for automotive interiors. In various embodiments of the present invention, the adhesive formulation is utilized as a hot melt adhesive and comprises at least one copolymer of the present invention and at least one tackifier resin. Optionally, the hot melt adhesive may further comprise a wax, optionally an oil, and / or an antioxidant. In one particular embodiment, the hot melt adhesive comprises about 40 to about 85% by weight of the copolymer of the present invention and about 15 to about 45% by weight of the tackifier resin. In another embodiment, the hot melt adhesive composition does not comprise a tackifier resin.
[0182] One embodiment of the present invention relates to a vehicle having a vehicle interior material (preferably an automobile interior material) including a skin material (preferably a polyolefin-based substrate) to which a hot melt composition is applied. Examples of the vehicle according to the present invention include, but are not limited to, automobiles, motorcycles, buses, and streetcars. In this specification, the term "automobile interior material" is used in some sentences, but it can be interpreted as meaning an interior material for vehicles other than automobiles as long as the hot melt composition of the present invention can be applied.
[0183] The compositions of the present invention can be used to form bonds to produce laminates and multi-layer laminates. The terms "laminate" and "multi-layer laminate" are used interchangeably.
[0184] The inventive composition according to one or more embodiments of the present invention can be bonded to a variety of adherends, including, but not limited to, cellulosic polymeric materials such as paper, cotton, linen, cloth, and wood boards; polyolefin resins such as polypropylene and polyethylene, styrene resins such as polystyrene, styrene-butadiene block copolymers (SBS resins), styrene-acrylonitrile copolymers (AS resins), acrylonitrile-ethylene / propylene-styrene copolymers (AES resins), and acrylonitrile-butadiene-styrene copolymers (ABS resins), polycarbonate resins (PC resins), (meth)acrylic resins, polyester resins, polyamide resins such as nylon and polyurethane, phenolic resins, and epoxy resins. The material of the adherend can be a mixture or combination of two or more different materials. When forming a laminate by bonding two different adherends through an adhesive layer comprising the inventive propylene-ethylene polymer or the inventive hot melt adhesive, the materials of the two adherends can be the same or different from each other.
[0185] Laminates containing the polymer or composition of the present invention can be suitably used in applications in which coating materials and formed articles are used as adherends, such as interior materials for automobiles and the like (e.g., automobile interior ceiling materials, automobile interior door parts, automobile interior dashboard parts, instrument panels), home appliance parts (e.g., personal computer housings, flat-screen television frames), and housing materials (e.g., interior wall panels, decorative films).
[0186] Covering materials refer to any type of film, sheet, foam, or nonwoven or woven material. Examples include decorative polymer sheets made of polyvinyl chloride, various polyolefins, or ABS, thermoplastic polyolefin compounds (TPO), such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, polyester nonwoven fabrics, brushed knits, woven fabrics, polyurethane artificial leather, and polyolefin foams made mainly of polypropylene, polyethylene, polybutylene, or copolymers of these olefins. Examples of molded products include injection molded products of various polymer materials such as ABS, PC / ABS, polyolefin, glass fiber reinforced polyolefin, and glass fiber reinforced nylon; wood molded products and wood boards prepared by enveloping materials such as wood chips or wood powder in thermosetting resin or polyolefin resin by hot press molding.
[0187] When preparing a multi-layer laminate by bonding a coating material such as a decorative sheet to a molded article used as a substrate through an adhesive layer containing the propylene-ethylene polymer or hot melt adhesive composition of the present invention, various forming methods such as heat lamination, vacuum forming, vacuum pressure forming, hot pressing, hot rolling, hot stamping, etc. A curved molded article refers to a molded article made from the above material, in which the bonding surface with the coating material has a flat arc-shaped surface. Such a molded article is used to form a shape framework in an automobile interior or a housing of a home appliance.
[0188] In other embodiments of the present invention, adhesive composition formulations are provided. Each of the following embodiments contains an inventive propylene-ethylene copolymer as previously described in this disclosure.
[0189] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising at least one propylene-ethylene copolymer, wherein the propylene-ethylene copolymer comprises ethylene and propylene, the amount of propylene being in the range of about 89 to about 95% by weight, the ethylene-propylene copolymer having a Ring and Ball softening point of about 135 to 160° C., the ethylene-propylene copolymer having a triad stereoregularity of about 50 to about 70%, and the composition comprising: (a) 5 to 100 weight percent of at least one propylene-ethylene copolymer; (b) 0 to 55 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 35 weight percent of at least one wax.
[0190] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition, comprising: (a) 5 to 100 weight percent of at least one propylene-ethylene copolymer; (b) 0 to 50 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 35 weight percent of at least one wax.
[0191] These adhesive compositions may have a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 177°C, and / or a shear adhesion failure temperature of at least about 135°C, and / or a thermal creep length of 5 mm or less at 110°C, and / or a thermal creep length of 5 mm or less at 120°C.
[0192] These adhesive compositions may have a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 190°C, and / or a shear adhesion failure temperature of at least about 135°C, and / or a thermal creep length of 5 mm or less at 110°C, and / or a thermal creep length of 5 mm or less at 120°C.
[0193] In certain embodiments, or in combination with any of the embodiments mentioned herein, these adhesive compositions may have a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 177° C., and / or a shear adhesion failure temperature of at least about 135° C., and / or a thermal creep length of 5 mm or less at a temperature at least 10° C. higher than the temperature at which a comparable composition not comprising at least one propylene-ethylene copolymer has a thermal creep length of 5 mm or less.
[0194] In certain embodiments, or in combination with any of the embodiments mentioned herein, these adhesive compositions may have a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 190° C., and / or a shear adhesion failure temperature of at least about 135° C., and / or a thermal creep length of 5 mm or less at a temperature at least 10° C. higher than the temperature at which a comparable composition not comprising at least one propylene-ethylene copolymer has a thermal creep length of 5 mm or less.
[0195] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 10 to 70 weight percent of at least one propylene-ethylene copolymer; (b) 5 to 55 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 20 weight percent of at least one wax.
[0196] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 5 to 95 weight percent of at least one propylene-ethylene copolymer; (b) 5 to 90 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 20 weight percent of at least one wax.
[0197] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 30 to 80 weight percent of at least one propylene-ethylene copolymer; (b) 1 to 45 weight percent of at least one second polymer; and (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 20 weight percent of at least one wax.
[0198] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 35 to 85 weight percent of at least one propylene-ethylene copolymer; (b) 0 to 45 weight percent of at least one second polymer; (c) 5 to 35 weight percent of at least one tackifier; (d) 33 percent by weight or less of at least one wax; (e) up to 17 weight percent of at least one polypropylene wax.
[0199] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 35 to 85 weight percent of at least one propylene-ethylene copolymer; (b) 0 to 45 weight percent of at least one second polymer; (c) 5 to 35 weight percent of at least one tackifier; (d) up to 26 weight percent of at least one polyethylene wax; and (e) up to 7 weight percent of at least one polypropylene wax.
[0200] In one embodiment, or in combination with any embodiment mentioned herein, there is provided an adhesive composition comprising: (a) 50 to 95 weight percent of at least one propylene-ethylene copolymer; (b) 0 to 55 weight percent of at least one second polymer; (c) 5 to 35 weight percent of at least one tackifier; (d) 0 to 15 weight percent of at least one wax.
[0201] In any of these adhesive compositions, the composition may be selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor ready polyolefins, metallocene catalyzed polyolefin polymers and elastomers, reactor made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene catalyzed polypropylene polymers, metallocene catalyzed polyethylene polymers, propylene based terpolymers including ethylene-propylene-butylene terpolymers, propylene and linear or branched C4-C10 Copolymers made from alpha-olefin monomers, ethylene and linear or branched C4-C 10 The composition may further comprise at least one second polymer selected from the group consisting of copolymers produced from alpha-olefin monomers, functionalized polyolefins, isoprene-based block copolymers; butadiene-based block copolymers; hydrogenated block copolymers; styrene-ethylene / butylene-styrene block copolymers (SEBS); styrene-isoprene-styrene block copolymers (SIS); styrene-ethylene / propylene-styrene (SEPS); ethylene vinyl acetate copolymers; polyesters; polyester-based copolymers; neoprene; urethanes; acrylics; polyacrylates; acrylate copolymers, such as, but not limited to, ethylene acrylic acid copolymers, ethylene n-butyl acrylate copolymers, and ethylene methyl acrylate copolymers; polyether ether ketones; polyamides; styrene block copolymers; hydrogenated styrene block copolymers; random styrene copolymers; ethylene-propylene rubber; ethylene vinyl acetate copolymers; butyl rubber; styrene butadiene rubber; butadiene acrylonitrile rubber; natural rubber; polyisoprene; polyisobutylene; and polyvinyl acetate.
[0202] In one embodiment, or in combination with any embodiment mentioned herein, there is provided a process for making an adhesive composition comprising the steps of: (a) from 5 to 100 weight percent of at least one propylene-ethylene copolymer, the propylene-ethylene copolymer comprising ethylene and propylene, the amount of propylene being in the range of from about 89 to about 95 weight percent, the ethylene-propylene copolymer having a Ring and Ball softening point of from about 135 to 160° C., and the ethylene-propylene copolymer having a triad stereoregularity of from about 50 to about 70 percent; (b) 0 to 55 weight percent of at least one second polymer; (c) 70 weight percent or less of at least one tackifier; (d) 20 percent by weight or less of a processing oil; (e) up to 35 weight percent of at least one wax.
[0203] In this process, the adhesive composition can be used to bond to a substrate and subsequently laminate to another substrate.
[0204] In one embodiment, or in combination with any embodiment mentioned herein, there is provided a process for preparing an automobile assembly, comprising: (a) applying an adhesive composition to a surface of at least one layer of a substrate; (b) forming a laminate by contacting the surfaces to be bonded together.
[0205] The adhesive composition can be used to produce a variety of articles, including articles including adhesives, sealants, caulkings, roofing membranes, waterproofing membranes, compounds and underlayments, carpets, laminates, laminate articles, tapes, labels, mastics, polymer blends, wire coatings, molded articles, heat seal coatings, disposable sanitary articles, insulating glass (IG) units, bridge decks, bitumen modification, asphalt modification, electronic enclosures, waterproofing membranes, cable flooding / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision casting, investment casting wax compositions, bookbinding, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles, and the like. and the adhesive comprises a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile wrapping adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible lamination adhesive, a rigid lamination adhesive, a flexible film adhesive, a flexible packaging adhesive, a water activated adhesive, a household repair adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a cling film, a lamination adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive, and a sanitary elastic attachment adhesive.
[0206] The present invention can be further illustrated by the following examples of these embodiments, it being understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless specifically stated.
[0207] Working Example Polymerization of heat-resistant propylene-ethylene copolymers A variety of inventive propylene-ethylene copolymers were produced having specific propylene contents, desirable triad tacticities (mm%) (i.e., reflecting isotactic structures), and high ring and ball softening points (RBSP). The propylene-ethylene copolymers were produced according to the following polymerization process.
[0208] The reactants propylene, ethylene, and hydrogen, along with diluent, external donor, and catalyst, were fed to a 5 gallon continuously stirred tank reactor (CSTR) at the ratios, flow rates, and temperatures provided in Tables 2A, 2B, and 2C for each of the samples produced. The inventive and comparative samples (i.e., comparative samples produced) in Tables 3A and 3B were made with a third generation (benzoate) catalyst and an alkoxysilane as the external electron donor as described above, and the inventive and comparative samples in Table 3C were made with fifth and sixth generation catalysts, both with and without the external electron donor as described above. The reactor was operated at pressures ranging from 790 to 850 psi. In addition, a hot oil system provided tracing of the reactor jacket. A dip tube conveyed product from the reactor, and an equilibar (pressurized by helium) maintained pressure control of the reactor.
[0209] The copolymer from the letdown tank was then stripped of diluent and then deactivated of residual catalyst in a hot oil jacketed exchanger using steam and nitrogen. The molten copolymer was then collected from the bottom of the deactivator and pumped to a final product collection tank.
[0210] The resulting copolymers in Table 1 were prepared as described above using the conditions listed in Tables 2A, 2B, and 2C. The properties of the resulting copolymers from the conditions given in Tables 2A, 2B, and 2C are shown in Tables 3A, 3B, and 3C.
[0211] The inventive examples in Tables 2A, 3A, 2B, and 3B were produced using the aforementioned third or fourth generation ZN catalyst systems and external electron donors. In comparison to Comparative Examples 1-6, the combination of a donor ratio of less than about 1:1 and an ethylene flow rate of less than 40 g / hr unexpectedly resulted in a ring and ball softening point of greater than 135° C., with a penetration typically less than about 21, and a tensile strength typically greater than about 2.5 MPa.
[0212] As shown in Tables 3A and 3B, the addition of an external donor generally increases hardness, which is indicated by a decrease in needle penetration along with an increase in the viscosity of the copolymer. In addition, a reduction in ethylene flow rate results in a copolymer with a high propylene to ethylene comonomer ratio, thus increasing the RBSP and hardness, which is indicated by a decrease in needle penetration. Compared to Comparative Example 6 (Example C1 from Eastman Chemical Company's U.S. Pat. No. 942,859), the inventive examples were produced with a lower relative ethylene flow rate (referring to a lower relative ethylene flow rate at an equivalent propylene flow rate) and the use of an external donor. As shown in Table 3, the copolymer of the inventive Example 1 was observed to have about a 20% increase in ring and ball softening point (RBSP) and about a 95% decrease in needle penetration compared to Comparative Example 6.
[0213] Unexpectedly, the polymers of the present invention, having a low ethylene content of about 2% to about 11% by weight and a test stereoregularity content of about 50% to about 70% (mm% by proton NMR), simultaneously have high RBSP (heat resistance) and high tensile. Additionally, the polymers of the present invention have a surprisingly wide viscosity range of about 2000 cP to about 50000 cP at 190°C.
[0214] The copolymers of the present invention and comparative samples produced under the conditions provided in Tables 2A, 2B, and 2C were subjected to testing to verify the properties and characteristics of the copolymers. Unless otherwise stated, various properties were tested using the test methods described.
[0215] Techniques for determining ethylene and propylene composition by NMR can be found in Macromolecules 2000, 33, 1157-1162 (Wang et al), and equations for measuring triad tacticity can be found in U.S. Pat. No. 5,504,172 and in the paper by Tsutsui et al. (Polymer 1989, 30, 1350-1356), all of which are incorporated by reference in their entireties.
[0216] Samples were prepared by adding 0.4 g of polyolefin sample and 100 mg of Cr(acac)3 to a 4-dram vial, followed by 0.5 mL of orthodichlorobenzene-d4 and 3.5 mL of trichlorobenzene (non-deuterated). The resulting solution was magnetically stirred at 120 °C until complete dissolution of the copolymer was observed by visual inspection. Dissolution was typically complete within 1 h. A 10 mm NMR tube was warmed to 80 °C. While wearing heat-resistant gloves, the warm solution was poured into a 10 mm NMR tube until the sample height was approximately 4.5-5 cm. The tube was then capped with a push-on cap. It was important to transfer the solution into the NMR tube while still warm so that it did not solidify before the transfer was complete. Spectra were analyzed using MNova software. After applying a Fourier transform to the FID data, the spectra were phased and baseline corrected, and calculations were performed as described in the references given. The standard deviation in PP% was determined to be 0.7 and the standard deviation in mm% was determined to be 0.3. The standard deviation in PP% was determined to be 0.7 and in mm% to be 0.3.
[0217] The triad tacticity of a polymer is the relative tacticity of the sequence of three adjacent propylene units, a chain consisting of head-to-tail bonds, expressed as a binary combination of meso (m) and racemic (r) sequences. The triad tacticity, expressed herein as "mm %, " was determined by 13C nuclear magnetic resonance (NMR) and the following formula:
[0218]
number
[0219] [ka] The triad tacticity of polypropylene depends on the relative tacticity of the sequence of three adjacent propylene units.
[0220] For comparative purposes, Table 3D provides the properties of various commercially available copolymers ("CACs") and commercial waxes.
[0221] [Table 3]
[0222] [Table 4]
[0223] [Table 5]
[0224] [Table 6]
[0225] [Table 7]
[0226] [Table 8]
[0227] [Table 9]
[0228] As demonstrated in Table 3D, many commercially available copolymers are available with softening points that overlap with the copolymers of the present invention. However, as shown in Figure 1, these commercially available copolymers exhibit one or more defects that limit their use in high heat resistance applications. In addition, commercially available high crystallinity low molecular weight waxes with high crystallinity, such as those shown in Table 3D, can be added to improve the heat resistance properties of the adhesive. As shown in Table 3D and Figure 1, these commercially available waxes may exhibit ideal softening points, but they are very brittle (as shown by the heat of crystallization). Therefore, there are some common problems with blending polyolefins with these waxes due to their brittleness. As a result, the use of these waxes can negatively affect the viscosity and cohesive strength of the resulting adhesive.
[0229] As shown in FIG. 1, the copolymers of the present invention in Tables 3A-3C had superior crystallinity and softening points relative to the commercial copolymers and waxes in Table 3D.
[0230] Hot Melt Compositions, Laminates, and Bond Formation and Experimental Procedures for Testing
[0231] [Table 10]
[0232] [Table 11]
[0233] Preparation of Hot Melt Adhesive Compositions The heating block was preheated to approximately 180°C. The polymer, wax, resin, and antioxidant were weighed into a 1 pint aluminum container. The container was then placed in a heating mantle. Once the mixture showed signs of melting, a stir bar was inserted and mixed at a speed of approximately 150 rpm until uniform. The adhesive was poured onto silicon coated release paper and allowed to cool to room temperature.
[0234] Viscosity measurement hot melt adhesive Viscosity was measured using a Brookfield DV2 Textra Viscometer equipped with a Thermosel™ and a number 27 spindle according to internal method per ASTM D-3236. 10.5 grams of adhesive was placed in a Brookfield tube and the sample was heated to temperature (if not melted) for 10 minutes. The sample was then allowed to equilibrate under shear for 20 minutes at each respective test temperature. The spindle rpm was adjusted to maximize motor % and no adjustments were made during the last 20 minutes of the shear equilibration period. Values are reported in centipoise (cP). Viscosity readings were taken from low to high temperature.
[0235] Adhesive ring and ball softening point (RBSP) Adhesive ring and ball softening point was measured using a Herzog ring and ball softening point apparatus according to ASTM method E-28. The formulated adhesive was decanted onto a brass ring and allowed to cool overnight or for >16 hours. Samples were trimmed flat before testing. The silicone oil was heated at 5°C per minute until the ball passed through the softened specimen, at which point the temperature was measured. The reported value is the average of two readings.
[0236] Adhesive Open Time Measurement Laboratory open time determinations were made using an internal method based on ASTM D4497-10 "Determining the open time of hot melt adhesives". The molten adhesive (180°C) was applied as a 127 or 635 μm (5 or 25 mil) film using a hot drawdown bar onto kraft paper. The final film thickness was 3-5 mil (0.1 mm) or 20-25 mil (0.5 mm). The paper strips were pressed against the film by a 1 kg weighted block at certain intervals (depending on the open time). Thirty minutes after the last strip was applied, a 90° peel was performed by hand to determine which of the applied strips could be removed without pulling out the paper fibers (50% fiber tear). The time this strip was applied was recorded and the open time was calculated.
[0237] Preparation of polymer samples for tensile strength measurements Preparation of tensile strength samples: A Carver press was used to prepare film samples for tensile testing. 20 grams of molten sample was placed into a 5" x 5" (137mm x 137mm) aluminum square mold frame with a thickness of 1mm. The sample was then sandwiched between silicone coated PET film, release paper, and metal board, and then heated in the Carver press with zero pressure applied. The sample was held at 177°C-188°C for 12 minutes, then 6000 PSI of pressure was applied for 5 seconds and released, then the pressure was increased to 12000 PSI and released again. Finally, 18000 PSI of pressure was applied and held for 2 minutes. The sample was then removed from the press and quickly transferred from the hot metal plate to a set of room temperature plates with a 10 kg weight block on top to act as a heat sink. After a cooling time of 8 minutes, the block and metal plate were removed. The resulting 137 mm x 137 mm x 1 mm films were stored in a controlled temperature and humidity room (25°C, 50% RH) for 24 hours and then cut using a dumbbell-shaped cutter based on ASTM-D412 die C.
[0238] Polymer Tensile Strength Measurement Tensile test: Tensile strength and elongation at break were measured at 20 in / min (51 cm / min) according to the procedure described in ASTM D412 (Die C). All tests were performed in a temperature and humidity controlled (CTH) room at 25C and 50% RH. Tensile strength at break was calculated by dividing the force magnitude at break by the cross-sectional area of the unstrained specimen. Elongation at break was calculated by the elongation distance recorded at break and normalized by the original standard gauge length of 62.5 mm in the tensile grips.
[0239] Melt Viscosity of Polyolefins The melt viscosity of the polyolefin polymers was measured at 190° C. using a Brookfield RVDVI+ viscometer with a number 27 spindle.
[0240] Performance measurement 1. Lamination of TPO foil and PP or ABS substrate 1.1 TPO-1 and PP or ABS The adhesive in an aluminum pan and a square film applicator (2 inch frame with 5-50 mil gap clearance) were heated in a 180°C oven for at least 30 minutes. The hot film applicator from the oven was placed on a TPO-1 sheet (approximately 9 inches by 5 inches) and the molten adhesive was immediately poured onto the inside of the applicator. A 5 mil thick film of adhesive was then drawn down onto the TPO-1 foil. After cooling, the coated foil was cut to widths of 1.0 inch or greater for bonding to PP or ABS substrates.
[0241] The above TPO-1 foil with pre-coated adhesive was placed in a 175° C. oven with the adhesive layer facing up, then a PP or ABS substrate with size 4 inches×1 inch and ⅛ inch thickness was placed on the coated TPO-1, followed by a 1 kg weight. After the oven door was closed for 2 minutes, the TPO-1 / PP or TPO-1 / ABS laminate was removed from the oven and allowed to cool to room temperature.
[0242] 1.2 TPO-2 and PP The adhesive, molten at 180°C, was introduced into a 2 inch square film applicator with a 5 mil gap clearance, and then a film of adhesive 2 inches wide and approximately 10 inches long was drawn down onto the silicone paper. The silicone paper was cut to a size of 2 inches long and over 1 inch wide, with the adhesive film attached to one end of the paper. The TPO-2 foil was cut into a piece approximately 5.5 inches long and 1 inch wide. A bottom-to-top assembly was then made of the film on silicone paper, TPO-2 (contact layer down and decorative layer up), and weight, and then placed on a hot plate with a surface temperature of approximately 180°C. After 15 seconds, the assembly was removed from the hot plate and allowed to cool. The silicone paper was carefully removed, resulting in an adhesive film coated onto the TPO-2 foil with a coating weight of 60-80 gsm (grams per square meter).
[0243] The adhesive pre-coated TPO-2 foil was placed under an IR heater (Chromalox CPL-0612) for 25 seconds so that the adhesive surface reached 140° C. or higher. Immediately, a PP substrate (4″×1″×1 / 8″ in size) was placed on top of the adhesive. The PP / TPO-2 laminate was removed from the IR heating area and a 2 kg weight was applied.
[0244] 2. Shear Adhesion Failure Temperature (SAFT) 2.1 PP and PP, 1kg SAFT The shear adhesion failure temperature (SAFT) was tested on two PP substrates (2" x 1") size bonded with an adhesive. The adhesive was melted at 180-200°C for at least 20 minutes and then applied to one surface of the PP substrate with a laboratory spatula. Another PP substrate was immediately placed on top of the adhesive and gentle pressure was applied to ensure a bonded area of 1" x 1". A 1kg weight was placed on the bonded area for at least 1 hour. The adhesive thickness was 0.5-0.7mm. After cooling, the excess adhesive was removed with a knife.
[0245] SAFT temperature measurements followed ASTM D4498-07 "Standard Test Method for Heat-Fail Temperature in Shear of hot Melt Adhesives". After conditioning at room temperature for at least 24 hours, the specimens were placed in a programmable oven equipped with a Cheminstruments 30-Bank testing machine (West Chester Township, OH). The static load was 1 kg. The heating program was set to run from 20°C to 150°C at a ramp rate of 0.5°C / min. The program recorded the time when the bond broke (the weight dropped) and converted to the bond failure temperature. A total of five specimens were tested and the average was reported.
[0246] 2.2 Birch and birch, 500g SAFT The procedure was the same as for the PP / PP bond, except a birch / birch substrate was used. A static load of 500 grams was used for the measurements.
[0247] 2.3 Kraft paper and kraft paper, 500g (packaging SAFT) SAFT values were obtained following ASTM D4498-07 "Standard Test Method for Heat-Fail Temperature in Shear of hot Melt Adhesives" for internal procedures for sample preparation and temperature measurement. Two sheets of kraft paper approximately 6 inches wide by 14 inches long were placed on a work surface with the inside of the kraft paper roll facing up. An 8 inch wide by 14 inch long bonding template with a 1 inch wide by 12 inch long opening was placed on top of one sheet of kraft paper and the template was held in place. The adhesive was melted at 180-200°C for at least 20 minutes and an approximately 1 / 4 inch wide bead of adhesive was decanted onto the kraft paper within the template opening. A second sheet of kraft was placed on top of the adhesive with its inside surface down. A 4.5 pound hand roller was used to roll two passes over the bond line. The bonded kraft paper was cut into 1 inch wide strips and the strips were conditioned in a constant temperature and humidity (CTH) room for 24 hours prior to testing. Standard CTH conditions are 70°F + / - 3°F (21°C + / - 2°C) and 50% (±5%) relative humidity.
[0248] The substrate was 40 lb virgin kraft paper. The adhesive thickness was approximately 15-20 mils and the bond area was 1 in. x 1 in. A static load of 500 g was used in a programmable oven equipped Cheminstruments 30-Bank tester with a heating rate of 0.5° C. / min according to ASTM D4498.
[0249] 3.180 degree peel strength The 180 degree peel strength of laminated PP / TPO or ABS / TPO (TPO-1 or TPO-2) was measured at a speed of 300 mm / min on an MTS Criterion Model 43 Electromechanical Universal Test System. The bonds were aged for at least 24 hours before peel strength determination. The substrate size was 4 inches by 1 inch. After each measurement, the peeled specimens were observed and failure modes were recorded, including cohesive failure (Coh), adhesive failure (Adh), mixed adhesive and cohesive failure (A+C), adhesion failure to foil (AFF), adhesion failure to substrate (AFS), and TPO foil failure (FF).
[0250] When 180 degree peel strength was tested at 90° C. or 120° C., the aged specimens were peeled using an MTS testing machine placed in a thermal chamber at the corresponding temperature. The specimens remained in this chamber for 5 minutes before measurement.
[0251] 4. Thermal creep test 4.1 Lamination of PP and TPO-2 The lamination of PP and TPO-2 was the same with 180 degree peel strength and bond length of about 2 inches (50 mm). After bonding, the laminate PP / TPO-2 with size 4 inches x 1 inch and bond area 2 inches x 1 inch was clamped on one end of the PP at room temperature for more than 24 hours. A 100 gram weight was then attached to the TPO foil so that the TPO and substrate PP were at a 90 degree angle when the laminate was tested. The laminate was placed in an oven at a preset temperature for 24 hours. After 24 hours, the TPO peel distance from the PP was measured and recorded as the creep length. Triplicate specimens were tested and an average creep length of 5 mm or less was indicated as a pass.
[0252] 4.2 Lamination of plywood and MDF board An adhesive film was prepared using a 6" x 6" PET frame with a thickness of 5 mils, which was placed under a Carver press with 0 psi applied pressure and maintained at 193°C for 1.5 minutes. After cooling, the adhesive film was cut into 1" x 4" pieces and placed on a 2" x 6" MDF board. A 1" x 4.5" piece of Tecofoil™ was placed on top of the adhesive piece and a metal board was placed on top of the Tecofoil. The assembled specimen was placed in the Carver press and pressed at 193°C with 0 psi until the adhesive piece melted and the MDF and Tecofoil were laminated together.
[0253] The specimens were allowed to rest for 24 hours, then secured to a test bracket and a 10 gram or 40 gram weight was attached to the Tecofoil tail to create a 90 degree angle between the MDF and the Tecofoil tail / weight. The test assembly was then placed in an oven at the desired starting temperature. The oven temperature was increased by 10°C per hour. When the peel distance of the Tecofoil from the MDF reached 7 cm, that temperature was recorded as the specimen failure temperature. Triplicate specimens were tested and the average failure temperature was reported.
[0254] 5. Dead load test Specimens for the dead load test were prepared according to General Motors specification GM 9986384 (purchased specification). Two polypropylene (PP-1) cubes measuring 1 inch x 1 inch x 1 inch and with a small hole in the center were bonded together by applying adhesive to one of the cubes and then mating it with the other cube. A 1 kg weight was placed on the bonded specimen until it reached room temperature. A total of three specimens were prepared with adhesive thicknesses of 0.5-0.7 mm.
[0255] The specimens were hung on a rack in an oven that was fitted with a weight, which was pre-determined at 200 g, 300 g, or 500 g, while the oven temperature was selected at 110° C., 120° C., or 130° C. If the bond did not break after 24 hours, it was recorded as a pass.
[0256] 6. Weathering or climate testing The climatic tests were selected according to BMW PR308.2 "Climatic test for bonded joints and composite materials on trim parts". The tests were performed in an Espec BTX-475 temperature and humidity chamber (ESPEC North America, Inc., Hudsonville, MI, USA). The tests consisted of 20 cycles, with the duration of one cycle being 12 hours. Each test cycle consisted of the following sequence: (a) heating from 23°C at 20% relative humidity (RH) for 1 hour; (b) at 90°C, 80% RH for 4 hours; (c) cooling and dehumidification for 1 hour; (d) at 23°C, 20% RH for 1 hour; (e) at -30°C for 4 hours; (f) heating to 23°C at 20% RH for 1 hour.
[0257] 7. Lap shear strength test The bonding procedure was as described above for the SAFT birch laminate, except the substrate size was 4 in. x 1 in. and the bond area was 1 in. x 0.5 in. Strength was measured on an MTS Criterion Model 43 Electromechanical Universal Test System at a speed of 12.7 mm / min. A minimum of five specimens of each sample were tested and the average value reported.
[0258] 8. Packaging cardboard fiber tear test Specimens for adhesion testing were prepared by applying a bead of 350°F (177°C) adhesive to the joining surface of the corrugated paper and immediately contacting it firmly with a piece of the inner surface of the corrugated paper. The cardboard flutes of the two substrates were vertical. The specimens were conditioned at room temperature for a minimum of 4 hours before testing, or the specimens were conditioned at room temperature overnight and then conditioned at 60°C for 4 hours ± 0.5 minutes to standardize for any migration of components that may affect adhesive performance. The bonded cardboard substrates were pulled apart by hand at room temperature or immediately after removal from the conditioning oven. The substrates were visually inspected and the percentage of fiber tear was estimated to the nearest 5%. At least three specimens were tested.
[0259] Table 5 lists the inventive propylene-ethylene copolymers used in the inventive compositions that were formulated and tested for application performance, including convenient family designations for the inventive copolymers from Tables 1A and 1B: (1) high viscosity, high tensile, and high RBSP polymers, (2) medium viscosity, high tensile, and high RBSP polymers, (3) very high viscosity and high RBSP polymers, and (4) low viscosity and high RBSP polymers. Table 6 lists the properties of the comparative polyolefin polymers tested with the corresponding polymer family designations based solely on the viscosity of the commercially available comparative polymer tested.
[0260] The inventive propylene-ethylene copolymers of Family 1 are preferred for sanitary adhesives. The propylene-ethylene copolymers of Family 2 and Family 3 are preferred for laminating, woodworking, and edge banding adhesives. Of particular note are the inventive propylene-ethylene copolymers in Family 4, inventive Examples 22, 23, and 24, which have lower viscosities (3,000-6,000 cp) and high RBSP, which were surprisingly useful for packaging adhesives. Table 5C also shows three commercially available polyolefin polymers used as comparative examples.
[0261] [Table 12]
[0262] [Table 13]
[0263] Inventive Examples 24 to 43 and Comparative Examples 10 to 12: Comparison of polymers in standard compositions All examples were prepared as described above in the Experimental Section "Preparation of Hot Melt Adhesives." The example compositions are given in weight percent (wt%) based on the weight of the total composition. The amount of antioxidant added was based on the total weight of the other ingredients.
[0264] Tables 7A, 7B, and 7C show the performance of inventive propylene-ethylene copolymers and comparative polymers in a typical formulation containing 70 wt. % polymer with the same types and amounts of tackifier resins, waxes, and antioxidants. The inventive examples exhibited high softening points from 142 to 151° C., high tensile strengths in the range of 3 MPa to 7 MPa, and high elongations (450 to 780%), except for inventive examples 3 and 4, which contained polymers with lower elongations.
[0265] The hot melt adhesive compositions of Examples 24-43 of the present invention demonstrated strong 180° peel strength when tested at 25°C, showing sufficient adhesive ability to bond polypropylene and TPO-1, substrates frequently used in automotive parts. The shear adhesion failure temperature (SAFT) measured by ASTM D4498 was surprisingly 124°C or higher, compared to Comparative Examples 7 or 8 (116°C and 95°C), illustrating that the polymers and adhesive compositions of the present invention have sufficient heat resistance at high temperatures for use in automotive interior parts and other applications requiring high heat resistance.
[0266] Inventive Examples 25-43 were prepared using inventive polymers from Family (1) and can be compared to Comparative Example 10, which was prepared using a commercial polymer in the same viscosity range.
[0267] The inventive examples include polymers having Ring and Ball softening points of 138-158°C, and surprisingly, the compounded compositions have RBSPs of 142-151°C, a reduction in RBSP of 7°C or less compared to the starting polymer. In contrast, comparative example 10, which includes a polymer having an RBSP of 161°C, results in a compounded composition having an RBSP of 150°C, a reduction in RBSP of 11°C. Comparing inventive examples 25-43 to comparative example 10, the RBSP of the compositions is maintained, allowing the inventive examples to be used in place of the comparative examples when an RBSP is specified for a product, while also allowing for improved composition properties, as discussed below.
[0268] While maintaining a similar RBSP as Comparative Example 10, Inventive Examples 25-43 had viscosities of about 6800 cP to about 12500 cP at 190°C, a surprising 57% lower than Comparative Example 10, allowing for better processing, lower add-on amounts, or the potential for lower application temperatures, among other commercial benefits. Surprisingly, Inventive Examples 25-43 all had SAFT values measured on a PP-PP basis as described above that were about 9 to about 28% greater than Comparative Example 10, with SAFT values ranging from about 125°C to about 150°C.
[0269] The inventive examples maintained or even exceeded the 180 degree peel strength between PP and TPO-1 foil substrates at 25° C., with inventive Example 43 having a surprisingly 91% greater peel strength than Comparative Example 10, with peel values as high as about 80 N / 25 mm at 25° C. for the particular substrate and test conditions. Unexpectedly, the inventive examples had peel strengths as high as 188% (Inventive Example 40) than Comparative Example 10, with peel values as high as about 5 N / 25 mm at 90° C.
[0270] Inventive Examples 25-43 also have tensiles that are about 42% to about 250% greater than the comparative examples, while some inventive examples have comparable elongations at break that are less than 20% lower than the elongations at break of the comparative examples.
[0271] Inventive Examples 32, 35, 37, and 38 were prepared using inventive polymers from Family (2) and can be compared to Comparative Examples 11 and 12, each of which was prepared using a commercially available polymer in the same viscosity range.
[0272] For family (2), there was no difference between the RBSP shift polymer and the blended composition.
[0273] Inventive Examples 32, 35, 37, and 38 surprisingly have RBSPs 26-30% higher than Comparative Example 11, elongations at break of about 255-400% greater, and elongations at break of about 30%-45%. Inventive Examples 35, 37, and 38 surprisingly have 180° peel strengths at 90°C of about 69%-26% higher than Comparative Example 11, demonstrating improved performance in high heat environments. Additionally, inventive Examples 35, 37, and 38 also unexpectedly and simultaneously have
[0274] Compared with Comparative Example 11, PP / TPO-1 maintained a similar viscosity at 190°C and a similar 180° peel strength at 25°C. Inventive Examples 35, 37, and 38 have similar viscosities as Comparative Example 12, but unexpectedly had tensiles that were about 25% to about 50% higher. Inventive Examples 37 and 38 also have 180 degree peel strengths at 90°C, PP / TPO-1 that are 35 to 84% higher compared to Comparative Example 12, demonstrating improved performance in high heat environments.
[0275] [Table 14]
[0276] [Table 15]
[0277] [Table 16] NT = not tested
[0278] 2.High heat resistance A selection of pre-formulated compositions with viscosities of 9000-16000 cp and approximately 4000 cp at 190° C. are shown in Table 8. The open times of the examples of the present invention are greater than 40 seconds, which is an acceptable working time for many assembly, automotive, and woodworking applications. These open times can be further optimized by one of ordinary skill in the art, and the effect of varying the wax used in the composition is illustrated later in this disclosure.
[0279] In addition to forming an acceptable initial bond, it is desirable that the bond be maintained after exposure to an exterior environment, as simulated by tests known in the art as weathering or climate testing. The results in Table 8 are discussed below to illustrate the surprising retention of SAFT and peel strength of laminates PP / PTO-1 and ABS / TPO-1 after climate testing for compositions of the present invention.
[0280] Inventive Examples 25, 36, 38, 40, and 41 were prepared using inventive polymers from Family (1) and can be compared to Comparative Example 10, which was prepared using a polymer in the same viscosity range. All inventive examples had PP / PP SAFT temperatures about 20-25% higher than Comparative Example 10. The PP / TPO-1 180 degree peel strengths at 25° C. of about 51-86% higher, and the ABS / TPO-1 180 degree peel strengths at 25° C. of about 31% higher, indicate superior retention of heat resistant properties after weathering, compared to Comparative Example 10.
[0281] As is typical, all examples had lower SAFT and peel values after the weathering / climate test cycle. However, after weathering, inventive Example 36 unexpectedly had about 27% higher PP / PP SAFT temperature, and about 27% higher PP / TPO-1 180 degree peel strength at 25° C. Inventive Examples 25, 36, 38, and 41 also unexpectedly had about 18-36% higher ABS / TPO-1 180 degree peel strength at 25° C., demonstrating superior retention of heat resistant properties after weathering, as compared to Comparative Example 10.
[0282] Inventive Examples 37 and 39 were prepared using inventive polymers from family (2) and can be compared with Comparative Examples 11 and 12. The compounding viscosities were comparable. Inventive Examples 37 and 39 have SAFT, PP / PP values about 45% higher than Comparative Example 11. As with the examples from polymer family (1), all examples had lower SAFT and peel values after weathering / climate testing cycles. Comparative Example 11 lost about 86% of its 180° peel strength, PP / TPO-1 and ABS / TPO-1 at 25°C. Inventive Examples 37 and 39 and Comparative Example 12 all maintained acceptable 180° peel strength, PP / TPO-1 and ABS / TPO-1 at 25°C after weathering / climate exposure. Although Comparative Example 12 had a higher starting SAFT, PP / PP value, Inventive Example 39 unexpectedly had a higher SAFT, PP / PP after climate testing (about 5%) than Comparative Example 12.
[0283] [Table 17] NT = not tested
[0284] Tables 9A and 9B show the peel strength PP / TPO-2 measured at temperatures between 25°C and 120°C. The peel strengths at 25°C for the inventive and comparative examples are similar since the bond exhibited foil failure (also called foam layer failure, FF) on the TPO-2 during peeling. At higher temperatures, 90°C and 120°C, most of the inventive example adhesives demonstrated surprisingly higher peel strength than the comparative examples, indicating that the inventive examples maintain strong cohesive strength behavior and high heat resistance capability. Inventive examples 25, 36, 38, 40, and 41 of family (1) have peel values at 90°C from about 109% to about 365% higher and at 120°C from about 220% to about 595% higher than Comparative Example 10. Most surprisingly and advantageously, inventive Example 38 had foil failure at 120°C compared to cohesive failure of the adhesive in Comparative Example 10, indicating that the adhesive of inventive Example 38 still had greater strength than TPO foil at this temperature.
[0285] After exposure to weathering agents in a climatic test, inventive Examples 38, 40, and 41 unexpectedly and advantageously exhibited 180 degree peel strength at 90°C, foil failure for PP / TPO-2, compared to cohesive failure of the adhesive in Comparative Examples 10 and 12 and the commercial adhesive Comparative Example 14. This resulted in peel strength values that were about 575% to about 660% higher than Comparative Example 10.
[0286] After exposure to weathering effects in a climatic test, inventive Example 38 most surprisingly and advantageously exhibited foil failure for 180° peel strength at 120°C, PP / TPO-2, compared to cohesive failure of the adhesive in Comparative Example 10, which had a peel strength value about 475% higher than Comparative Example 10. Inventive Examples 40 and 41 and Comparative Examples 10, 13 and the commercial adhesive Comparative Example 13 all exhibited cohesive failure. However, the 180° peel strength at 120°C, PP / TPO-2 of inventive Examples 40 and 41 were about 178% to about 211% higher than the peel value of Comparative Example 10, indicating that all of the inventive examples tested had excellent heat resistance and cohesive properties. Unexpectedly, inventive Example 40 had a 180° peel strength at 120°C, PP / TPO-2, about 84% higher and about 57% higher than the commercial adhesives tested as Comparative Examples 13 and 14. The inventors have found this to be particularly surprising since the formulations of the present examples were not optimized, whereas commercially available adhesives are.
[0287] [Table 18] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition, NT = not tested
[0288] [Table 19] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition, NT = not tested
[0289] Thermal creep measurements are a critical test for automotive parts, and reactive crosslinking adhesives are used where heat resistance of 120° C. is required. Tables 10A and 10B show the unexpected result that the heat resistant copolymers and hot melt compositions of the present invention can provide thermal creep resistance at 120° C. without crosslinking.
[0290] The measured values of thermal resistance by thermal creep and dead load tests are listed in Tables 10A and 10B. For thermal creep tests, the laminates were placed in an oven at a preset temperature for 24 hours. A pass was indicated if the average TPO peel distance (creep length) from PP was 5 mm or less (5 mm or less). All tested inventive examples containing polymers from families (1) and (2) passed the thermal creep at 90°C, while all comparative examples containing polymers from families (1) and (2) failed the thermal creep test at 90°C. Both Comparative Examples 13 and 14 of the two commercial adhesives passed the thermal creep at 90°C.
[0291] Both of the two commercial adhesives, Comparative Example 13 and Comparative Example 14, failed the thermal creep at 100°C. However, unexpectedly, inventive Examples 25, 36, 38, 40, and 41 passed at 100°C. Inventive Examples 25, 38, 40, and 41 passed at 110°C, and most surprisingly, inventive Examples 25, 38, and 40 passed at 120°C. Passing the thermal creep at 120°C is a "game changer" because it can replace reactive adhesives that crosslink. Some inventive example adhesive compositions passed thermal creep temperatures as high as 110°C and even 120°C, demonstrating strong resistance to higher temperatures. Unexpectedly, a positive correlation was found between the adhesive thermal creep failure temperature and peel strength at this temperature. This means that the higher the peel strength at the test temperature, the more likely it is to pass thermal creep at the same temperature.
[0292] In the dead load test, inventive Examples 25, 36, 38, 40, and 41 (Family 1 polymers), inventive Examples 37 and 39 (Family 2 polymers), and Comparative Example 12 passed the dead load test at 110° C. with a 200 g weight. Both Comparative Examples 10 and 11 failed the dead load test at 110° C. with a 200 g weight.
[0293] Inventive Examples 36, 38, 40, and 41 (Family 1 polymers), Inventive Examples 37 and 39 (Family 2 polymers) unexpectedly survived a 1 day dead load test at 130° C. with a 300 g weight. Surprisingly, Inventive Examples 36 and 40 passed 110° C. with a 500 g weight, and we were most surprised that Inventive Example 41 further passed 120° C. with 500 g, again demonstrating the excellent heat resistance performance of compositions containing the inventive polymers previously disclosed.
[0294] [Table 20]
[0295] [Table 21] NT = not tested
[0296] 3. Formulation variables 3.1 Tackifier resin Example adhesives of the present invention having the same copolymer but different tackifier resins were evaluated and are shown in Table 11. The listed ingredients are provided as weight percentages based on the total weight of the adhesive. The amount of antioxidant added was based on the total weight of the other ingredients. All adhesives showed strong peel strength even at higher temperatures, indicating that the copolymers of the present invention have very good compatibility with a wide range of hydrogenated C5, hydrogenated PMR, and hydrogenated C8 / C9 tackifier resins.
[0297] [Table 22] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition
[0298] 3.2 Waxes and acid-modified tackifier resins In Table 12, adhesives of inventive examples with the same copolymer and tackifier resin but different waxes were evaluated. The waxes included polypropylene (PP) wax with maleic anhydride grafted functional groups (inventive examples 44, 49-52) and PP wax without any functional groups (inventive examples 53 and 54). The wax viscosities at 190°C ranged from 150 cp to 18,000 cp and 60,000 cp. Due to the lower wax ratio in the formulation, the different waxes did not seem to change the performance of the adhesives very much, except for inventive example 50, where the maleic anhydride modified PP wax Eastman™ G3003 had a very high viscosity and contributed to the higher RBSP and stronger peel strength at 120°C.
[0299] Inventive Examples 53 and 54 contain non-functionalized / maleated wax. The effect of the lower softening point of the wax is seen in the lower SAFT of the composition. Surprisingly, inventive Example 54 maintains partial foil break at 90°C despite the lower softening point of the wax used, illustrating how the heat resistance of the inventive polymer in the composition maintains tensile strength, elongation at break, and 180° peel strength at 25°C and 90°C. Varying the wax type allows the formulator to adjust open time (40-70 seconds), needle penetration or hardness (3.5-4.2 dmm), adhesive RBSP (138-152°C), adhesive SAFT (135-148°C), and adhesive viscosity (8300-11000 cP at 190°C) to balance adhesive properties as needed. These examples are simple illustrations of using one additive level without varying other components, and one skilled in the art would be able to build on this knowledge.
[0300] [Table 23] MDP (Mettler Drop Point) = Mettler Drop Point, ASTM D-3954, reported on manufacturer's technical data sheet; Acid Number, ASTM D1386
[0301] In Table 13, the functional wax Epolene E43 was replaced with dimerized and partially dimerized rosin acid tackifier resins in the adhesive formulation. Rosin acids are compatible in the inventive copolymer formulations, and inventive Example 56, which has partially dimerized rosin acid, unexpectedly passed the thermal creep test at 100° C. The dimerized rosin acid did not show any improvement in adhesive adhesion at higher temperatures compared to the maleic anhydride grafted polypropylene wax based on the thermal creep test.
[0302] [Table 24]
[0303] The effect of the amount of wax on the adhesive properties and performance of the compositions is illustrated in Table 14. The ratio of inventive copolymer to tackifier resin was kept constant (70:25) in all formulations, the amount of acid functionalized PP wax Epolene™ E43 was increased from 0 to 30 wt% (inventive examples 57-60), and Epolene E43 was kept at 5 wt% and Epolene N15, used as the second unmodified PP wax, was increased from 5 to 15 wt% (inventive examples 61 and 62).
[0304] Surprisingly, it was discovered that inventive example 57 without wax not only maintained 180° peel strength PP / TPO-2 at 90°C with substrate foil / cohesive failure, but also passed the thermal creep test at 110°C. Maleated PP wax up to 20 wt% improved performance and reduced open time, while 30 wt% ma-PP wax reduced elongation. The combination of 5 wt% maleated PP wax with 15 wt% PP wax (inventive example 62) shows the formulation flexibility of the inventive copolymer, allowing for similar adjustment of adhesive open time and viscosity when lower elongation can be tolerated. Higher amounts of wax in the formulation reduced open time due to PP wax crystallization during cooling of the molten adhesive. Increasing the amount of wax also resulted in a decrease in viscosity and tensile elongation while increasing the softening point and SAFT.
[0305] [Table 25]
[0306] 3.3 Ratio of Copolymer of the Invention to Tackifier Resin In Tables 15A, 15B, and 16, the ratio of tackifier resin to inventive copolymer was varied through values of about 0:1, about 0.06:1, about 0.2:1, about 0.3:1, about 0.4:1, about 0.5:1, about 0.6:1, and about 0.9:1. Surprisingly, all inventive compositions with a ratio of tackifier resin to inventive copolymer less than 0.6:1 maintained an RBSP of about 140°C or higher and passed the thermal creep, PP / TPO-2 at 110°C. We were surprised that inventive Examples 38 and 64 passed the thermal creep, PP / TPO-2 at 120°C, which is typically only passed by crosslinked adhesives. Most unexpectedly, inventive Example 64 simultaneously passed the thermal creep, PP / TPO-2 at 120°C, and passed the dead load test, PP-1 / PP-1, 500g at 110°C for 1 day.
[0307] [Table 26]
[0308] [Table 27] NT = not tested, FF = foil failure (in the foam layer), Coh = cohesive failure of the adhesive composition
[0309] It was also noted that formulations with lower ratios of tackifier resin to copolymer of the invention passed higher temperatures in the thermal creep test, corresponding to increased peel strength at higher temperatures. This correlation provides formulators with the opportunity to balance the heat resistance and peel strength of their compositions by varying the amount of tackifier or by not using a tackifier resin.
[0310] [Table 28] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition, NT = not tested
[0311] 3.4 Blends with other polymers Tables 17, 18, and 19 show compositions of the invention in which the heat resistant propylene-ethylene copolymers of the invention are blended with styrenic block copolymers, amorphous polyolefin polymers, or metallocene catalyzed alpha-polyolefin polymers. The listed components are provided in weight percentages based on the total weight of the adhesive. The amount of antioxidant added was based on the total weight of the other components. These examples illustrate that these classes of polymers can be blended with the copolymers of the invention to maintain heat resistance and obtain an advantageous balance of properties. Those skilled in the art can use these formulations as a starting point for further formulations.
[0312] In the example adhesives shown in Table 17, Example 18 of the inventive copolymer was blended with Kraton G1643, a commercial triblock copolymer based on styrene and ethylene / butylene, at ratios of SEBS:inventive copolymer of about 0.09:1, about 0.14:1, and about 0.17:1. Inventive Example 40, a blend of the inventive copolymer and SEBS, had 180 degree peel strength at 90°C, foil failure with PP / TPO-2, passed the thermal creep test at 120°C, PP / TPO-1, and passed the dead load test at 110°C, PP-1 / PP-1, 1 day, 500 g, demonstrating surprising retention of heat resistance from the inventive copolymer in the composition.
[0313] The presence of SEBS polymer in formulations with tackifier resin and wax generally reduced the 120° C. heat resistance of the compositions of the invention as shown by cohesive failure in the 180° peel strength test at 120° C. and failure in the thermal creep test, PP / TPO-1, at 120° C. Inclusion of Epolene N-15 wax in compositions of the invention having both polymer and wax generally improved the peel performance.
[0314] [Table 29] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition, NT = not tested
[0315] In the inventive examples in Table 18, the heat-resistant copolymer inventive example 18 was blended with the commercial polymer Comparative Example 7 in different ratios, with or without additional wax. Unexpectedly, it was found that the addition of Comparative Example 7 to the inventive copolymer reduced the heat resistance of the adhesive composition. However, the results can be seen in the opposite direction, in that the inventive copolymer unexpectedly improved the heat resistance of the composition based on the polymer of Comparative Example 7. The addition of Epolene N15 wax seemed to improve the thermal creep performance, but reduced the dead load performance.
[0316] [Table 30] FF = foil failure (in the foam layer), coh = cohesive failure of the adhesive composition, adh = adhesive failure of the adhesive composition, NT = not tested
[0317] In the inventive example adhesives shown in Table 19, the copolymer of inventive example 18 was blended with a commercial copolymer produced by Ziegler-Natta catalyst (inventive example 82) or a commercial polyolefin copolymer produced by metallocene catalyst (inventive example 83). The inventive adhesives exhibited not only excellent tensile strength and elongation, but also a high SAFT of 22% greater than that of comparative example 10, and a 180 degree peel strength at 25°C of about 5% to about 66% greater than that of comparative example 10, PP / TPO-1, and a 180 degree peel strength at 90°C of about 69% to about 190% greater than that of comparative example 10, PP / TPO-1. Both the high SAFT and the higher peel strength at 90°C illustrate the surprising heat resistance of the formulations containing the novel propylene-ethylene copolymer. The inventors noted that inventive examples 40, 69, and 70 also surprisingly had a tensile strength of about 150% to about 260% greater than that of comparative example 10.
[0318] [Table 31]
[0319] 4. Woodworking applications Woodworking applications include profile wrapping, lamination, and other wood assemblies with veneers, papers, foils, and plastics. Adhesives need to have low odor, as well as higher heat resistance and greater cohesive strength than is typically available with currently commercially available polyolefin polymers. The propylene-ethylene heat resistant copolymers of the present invention address this need in woodworking adhesive formulations.
[0320] Tables 20A and 20B compare the heat resistance (measured by SAFT and 90 degree creep tests) and lap shear strength of selected inventive examples and Comparative Example 10, which include copolymers of the present invention.
[0321] Compared to Comparative Example 10, inventive Examples 33, 36, 37, 38, and 41 all unexpectedly had about 30% higher SAFT, about 8% to about 20% higher 90 degree creep rupture temperatures for the MDF board and Tecofoil V paper assembly, and about 80% to about 230% higher lap shear strengths, measured as specified in the table.
[0322] [Table 32]
[0323] [Table 33]
[0324] 5.Packaging applications Inventive Examples 8, 22, and 23 of the inventive heat resistant copolymers of family (4) having a viscosity of 3,000-6,000 cp at 190°C and an RBSP of greater than 140°C were surprisingly well suited for use in packaging adhesives, addressing the need for adhesives that are resistant to the high temperatures experienced by cases, cartons, and packages when stored in non-temperature controlled warehouses, especially when pallets of products are stacked high. Such adhesives can be used in boxes, cases, sealed cartons, and other applications where heat resistance is required. Illustrative formulations including low viscosity, heat resistant propylene-ethylene copolymers, tackifiers, and mixtures of PE wax, PP wax, and functionalized PP wax are shown in Tables 21A, 21B, and 21C. The formulations varied from 37% to 76% polymer, 5% to 35% tackifier resin, and 10% to about 33% total wax, resulting in compounded adhesive viscosities ranging from about 415 cP to about 4000 cP at 180°C. The level of maleated PP wax addition was either 2% or 5% based on the total weight of the formulation. The wax selection and ratio of PE wax, PP wax, and maleated PP wax used can be varied by one skilled in the art to adjust the balance of compounded adhesive viscosity, RBSP, SAFT, adhesion, and other properties. Baker-Hughes Polywax 850 (PE wax) has a melting point of 107°C and a viscosity of 10 cP at 150°C, per technical data sheet, and Honeywell MAPP AC-596 maleic anhydride copolymer has a Mettler dropping point (ASTM D-3954) of 141°C and a viscosity of 150 cP at 10°C, per technical data sheet. The examples given are not all inclusive, but illustrate the wide range of properties that can be obtained while maintaining heat resistance, as evidenced by the fiber tear performance at 60°C.
[0325] Inventive Examples 84, 89, and 96 had a polymer / tackifier / wax weight ratio of about 75 / 15 / 10 by weight and had a surprisingly desirable combination of viscosity for packaging applications, room temperature fiber tear on corrugated board, 60°C fiber tear on corrugated board, and shear bond failure temperature range. This composition also contributed the best fiber tear percentages tested at both room temperature and 60°C, and demonstrated excellent heat resistance based on SAFT (132°C-134°C).
[0326] Surprisingly, inventive Example 89, with a total wax content of nearly 17%, had excellent fiber tear at room temperature (93%) and 60°C (97%) and a SAFT of 134°C, with an overall formulation of 70 / 30 / 17 polymer / tackifier / wax.
[0327] Unexpectedly, inventive Examples 93 and 95 with the 50 / 27 / 23 blend had excellent 60°C fiber tear (92-98%) and acceptable room temperature fiber (55-65%) with very low viscosity (657-675 cP at 180°C) highly desirable for high speed packaging lines.
[0328] [Table 34]
[0329] [Table 35]
[0330] [Table 36]
[0331] definition It should be understood that the following is not intended to be an exhaustive list of defined terms. Other definitions may be provided in the preceding description, for example, as they accompany the use of a defined term in context.
[0332] As used herein, the terms "a," "an," and "the" mean one or more.
[0333] As used herein, the term "about" refers to any value within the range of 90% to 110% of the specified value. However, it should be noted that all values associated with "about" include support for the specific value itself and the range associated with the "about" specific value. For example, "about 10" provides support for the specific value of "10" and the range of values from 9 to 11. Furthermore, the term "about" can be associated with any specific value recited herein.
[0334] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition can contain only A, only B, only C, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B, and C.
[0335] As used in this specification, the terms "comprising," "comprises," and "comprise" are open-ended transitional terms used to transition from the subject matter described before the term to one or more elements described after the term, and the element or elements listed after the transitional term are not necessarily the only elements that make up the subject matter.
[0336] As used herein, the terms "having," "has," and "have" have the same open-ended meaning as "comprising," "comprises," and "comprise" provided above.
[0337] As used in this specification, the terms "including," "include," and "included" have the same open-ended meaning as "comprising," "comprises," and "comprise" provided above.
[0338] This description uses numerical ranges to quantify certain parameters related to the present invention. When numerical ranges are provided, it should be understood that such ranges are interpreted as providing literal support for claim limitations that recite only the lower limit of the range, as well as for claim limitations that recite only the upper limit of the range. For example, a disclosed numerical range of 10 to 100 provides literal support for claims that recite "greater than 10" (no upper limit) and claims that recite "less than 100" (no lower limit).
[0339] When a numerical sequence is presented, each number should be understood to be modified in the same manner as the first or last number in the sequence or sentence. For example, each number is "at least" or "less than or equal to," as the case may be, and each number is in an "or" relationship. In an exemplary scenario, "at least 10, 20, 30, 40, 50, 75 weight percent..." means the same as "at least 10 weight percent, or at least 20 weight percent, or at least 30 weight percent, or at least 40 weight percent, or at least 50 weight percent, or at least 75 weight percent."
[0340] The above preferred embodiments of the present invention should be used only as examples, and should not be used in a limiting sense to interpret the scope of the present invention. Modifications to the above exemplary embodiments can be easily made by those skilled in the art without departing from the spirit of the present invention.
[0341] The inventors hereby express their intention to rely on the doctrine of equivalents to determine and evaluate the reasonably fair scope of the present invention as it pertains to devices that are outside, but not substantially depart from, the literal scope of the invention as set forth in the following claims.
Claims
1. A propylene-ethylene copolymer comprising propylene and ethylene, the propylene-ethylene copolymer comprising: (a) containing 89 to 98 weight percent propylene; (b) having a Ring and Ball softening point of at least 135°C; (c) having at least 50 percent triad tacticity (mm %); (d) a propylene-ethylene copolymer having a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g.
2. 2. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer comprises 0.5 to 11 weight percent ethylene.
3. 2. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer has a viscosity of 1,000 to 50,000 cP at 190°C.
4. The propylene-ethylene copolymer is (a) having a viscosity of 2,000 to 7,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 1.5 to 8 MPa; and (d) a heat of crystallization of from 25 to 55 J / g.
5. The propylene-ethylene copolymer is (a) having a viscosity of 7,000 to 15,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 3 to 10 MPa; and (d) a heat of crystallization of from 25 to 55 J / g.
6. The propylene-ethylene copolymer is (a) having a viscosity of 15,000 to 27,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 3 to 14 MPa; and (d) a heat of crystallization of from 25 to 55 J / g.
7. The propylene-ethylene copolymer is (a) has a viscosity of greater than 27,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of at least 7 MPa; and (d) the propylene-ethylene copolymer of claim 1 exhibiting a heat of crystallization of from 25 to 50 J / g.
8. 2. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135 to 160°C.
9. 9. The propylene-ethylene copolymer of claim 8, wherein the propylene-ethylene copolymer has a triad stereoregularity in the range of 50 to 70 percent.
10. The propylene-ethylene copolymer of claim 9, wherein the propylene-ethylene copolymer has a penetration in the range of 0.1 to 21 dmm.
11. The propylene-ethylene copolymer of claim 10, wherein the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 to 14 MPa.
12. 12. The propylene-ethylene copolymer of claim 11, wherein the propylene-ethylene copolymer has an elongation at break of greater than 300 percent.
13. 2. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer has a heat of crystallization (Hc, cooling rate 20° C. / min) in the range of 20 to 55 J / g.
14. The propylene-ethylene copolymer is (a) exhibiting a penetration of 0.1 to 21 dmm; (b) having a heat of crystallization of 25 to 55 J / g; (c) the following: (i) having a viscosity of 2,000 to 7,000 cP at 190° C. and a tensile strength at break of 1.5 to 8 MPa; or (ii) having a viscosity of 7,000 to 15,000 cP at 190° C. and a tensile strength at break of 3 to 8 MPa; (iii) having a viscosity of 15,000 to 27,000 cP at 190° C. and a tensile strength at break of 3 to 14 MPa; or (iv) having one of the following characteristics: a viscosity greater than 27,000 cP at 190° C., a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 to 50 J / g.
15. The propylene-ethylene copolymer is (a) having a triad tacticity in the range of 53 to 78 percent; (b) exhibiting a ring and ball softening point of 135 to 165°C; (c) a heat of crystallization of 28 to 60 J / g.
16. The propylene-ethylene copolymer is (a) having a viscosity of 15,000 to 50,000 cP at 190° C.; (b) exhibiting a tensile strength at break of at least 3 MPa; (c) the propylene-ethylene copolymer of any one of claims 1 to 3 or 15, exhibiting an elongation at break of at least 300 percent.
17. A composition comprising the propylene-ethylene copolymer of claim 1.
18. 10. A process for producing the propylene-ethylene copolymer of claim 1, said process comprising polymerizing ethylene and propylene in the presence of a Ziegler-Natta catalyst system.
19. 1. An adhesive composition comprising: (a) from 5 to 100 weight percent of at least one propylene-ethylene copolymer, the propylene-ethylene copolymer comprising ethylene and propylene, the propylene-ethylene copolymer comprising: (i) containing 89 to 98 weight percent propylene; (ii) having a Ring and Ball softening point of at least 135°C; (iii) having a triad tacticity (mm%) of at least 50 percent; (iv) a propylene-ethylene copolymer having a heat of crystallization (Hc, cooling rate 20° C. / min) of at least 25 J / g; (b) 0 to 90 weight percent of at least one second polymer; (c) up to 70 weight percent of at least one tackifier; (d) 20 weight percent or less of a processing oil; and (e) up to 35 weight percent of at least one wax.
20. The adhesive composition of claim 19, wherein the adhesive composition comprises 5 to 55 weight percent of the second polymer.
21. The adhesive composition comprises: (a) a shear adhesion failure temperature of at least 135°C, and / or The adhesive composition according to claim 19, wherein (b) the adhesive composition has a thermal creep length of 5 mm or less at 110°C.
22. The adhesive composition comprises: (a) a shear adhesion failure temperature of at least 135°C; and The adhesive composition according to claim 19, wherein (b) the adhesive composition has a thermal creep length of 5 mm or less at 120°C.
23. The adhesive composition comprises: (a) 10 to 70 weight percent of said propylene-ethylene copolymer; (b) 5 to 55 weight percent of the second polymer; and (c) 70 weight percent or less of said tackifier; (d) 20 weight percent or less of said processing oil; 20. The adhesive composition of claim 19, comprising: (e) up to 20 weight percent of said wax.
24. The adhesive composition comprises: (a) 5 to 95 weight percent of said propylene-ethylene copolymer; (b) 5 to 90 weight percent of the second polymer; and (c) 70 weight percent or less of said tackifier; (d) 20 weight percent or less of said processing oil; 20. The adhesive composition of claim 19, comprising: (e) up to 20 weight percent of said wax.
25. The adhesive composition comprises: (a) 30 to 80 weight percent of said propylene-ethylene copolymer; (b) 1 to 45 weight percent of said second polymer; (c) 70 weight percent or less of said tackifier; (d) 20 weight percent or less of said processing oil; 20. The adhesive composition of claim 19, comprising: (e) up to 20 weight percent of said at least one wax.
26. The second polymer is selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor ready polyolefins, metallocene catalyzed polyolefin polymers and elastomers, reactor made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene catalyzed polypropylene polymers, metallocene catalyzed polyethylene polymers, propylene based terpolymers, copolymers formed from propylene and linear or branched C4 to C10 alpha-olefin monomers, copolymers formed from ethylene and linear or branched C4 to C10 alpha-olefin monomers, functionalized polyolefins, 20. The adhesive composition of claim 19, wherein the at least one polymer selected from the group consisting of styrene, isoprene-based block copolymers, butadiene-based block copolymers, hydrogenated block copolymers, styrene-ethylene / butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene / propylene-styrene (SEPS), ethylene vinyl acetate copolymers, polyesters, polyester-based copolymers, neoprene, urethanes, acrylics, polyacrylates, acrylate copolymers, polyether ether ketones, polyamides, hydrogenated styrene block copolymers, random styrene copolymers, ethylene-propylene rubbers, ethylene vinyl acetate copolymers, butyl rubbers, styrene butadiene rubbers, butadiene acrylonitrile rubbers, natural rubbers, polyisoprene, polyisobutylene, and polyvinyl acetate.
27. 20. The adhesive composition of claim 19, wherein the adhesive composition comprises less than 10 percent by weight of the wax.
28. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer comprises 0.5 to 11 weight percent ethylene.
29. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a viscosity of 1,000 to 50,000 cP at 190°C.
30. The propylene-ethylene copolymer is (a) having a viscosity of 2,000 to 7,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 1.5 to 8 MPa; and The adhesive composition of claim 19, which exhibits (d) a heat of crystallization of 25 to 55 J / g.
31. The propylene-ethylene copolymer is (a) having a viscosity of 7,000 to 15,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 3 to 10 MPa; and The adhesive composition of claim 19, which exhibits (d) a heat of crystallization of 25 to 55 J / g.
32. The propylene-ethylene copolymer is (a) having a viscosity of 15,000 to 27,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of 3 to 14 MPa; and The adhesive composition of claim 19, which exhibits (d) a heat of crystallization of 25 to 55 J / g.
33. The propylene-ethylene copolymer is (a) has a viscosity of greater than 27,000 cP at 190° C.; (b) exhibiting a penetration of 0.1 to 21 dmm; (c) a tensile strength at break of at least 7 MPa; and (d) the adhesive composition according to claim 19, exhibiting a heat of crystallization of 25 to 50 J / g.
34. 20. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135 to 160°C.
35. The adhesive composition of claim 34, wherein the propylene-ethylene copolymer has a triad stereoregularity in the range of 50 to 70 percent.
36. The adhesive composition of claim 35, wherein the propylene-ethylene copolymer has a penetration in the range of 0.1 to 21 dmm.
37. The adhesive composition of claim 36, wherein the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 to 14 MPa.
38. 38. The adhesive composition of claim 37, wherein the propylene-ethylene copolymer has an elongation at break of greater than 300 percent.
39. 20. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a heat of crystallization (Hc, cooling rate 20° C. / min) in the range of 20 to 55 J / g.
40. The propylene-ethylene copolymer is (a) exhibiting a penetration of 0.1 to 21 dmm; (b) having a heat of crystallization of 25 to 55 J / g; (c) the following: (i) having a viscosity of 2,000 to 7,000 cP at 190° C. and a tensile strength at break of 1.5 to 8 MPa; or (ii) having a viscosity of 7,000 to 15,000 cP at 190° C. and a tensile strength at break of 3 to 8 MPa; (iii) having a viscosity of 15,000 to 27,000 cP at 190° C. and a tensile strength at break of 3 to 14 MPa; or (iv) the adhesive composition according to claim 19, having one of the following characteristics: a viscosity of greater than 27,000 cP at 190° C., a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 to 50 J / g.
41. The propylene-ethylene copolymer is (a) having a triad tacticity in the range of 53 to 78 percent; (b) exhibiting a ring and ball softening point of 135 to 165°C; (c) the adhesive composition according to claim 19, exhibiting a heat of crystallization of 28 to 60 J / g.
42. The propylene-ethylene copolymer is (a) having a viscosity of 15,000 to 50,000 cP at 190° C.; (b) exhibiting a tensile strength at break of at least 3 MPa; 20. The adhesive composition of claim 19, wherein (c) the adhesive composition exhibits an elongation at break of at least 300 percent.
43. 43. An article comprising the adhesive composition of any one of claims 19 to 42, the article being an adhesive, sealant, caulking, roofing membrane, waterproofing membrane, compounds and underlayments, carpet, laminates, laminated articles, tapes, labels, mastics, polymer blends, wire coatings, molded articles, heat seal coatings, disposable sanitary articles, insulated glass (IG) units, bridge decks, bitumen modification, asphalt modification, electronic enclosures, waterproofing membranes, cable flooding / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision casting, investment casting wax compositions, bookbinding, candles, windows, tires, films, gaskets, seals, O-rings, automotive 16. The article of claim 15, wherein the adhesive is selected from the group consisting of automobiles, motorcycles, automotive molded parts, automotive extrusion parts, apparel, rubber additives / processing aids, and fibers, and the adhesive comprises a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile wrapping adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible lamination adhesive, a rigid lamination adhesive, a flexible film adhesive, a flexible packaging adhesive, a water activated adhesive, a household repair adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a cling film, a lamination adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive, or a sanitary elastic attachment adhesive.
Citation Information
Patent Citations
Low molecular weight propylene-based polymer and its production
JP1991084009A
Hot-melt adhesive composition
JP1991199282A
Propylene random copolymer-based hot melt adhesive composition
JP2021525825A
Amorphous propylene-ethylene copolymers
US20200332034A1
Propylene resin composition and use thereof
WO2006057361A1